Resin Sheet
The resin sheet with a specific metal foil support and inorganic filler composition addresses the issues of thickness uniformity and insulation reliability in vacuum pressing, resulting in improved performance of printed wiring boards and semiconductor devices.
Patent Information
- Application Number
- JP2021092421
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-01
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-06-01
AI Technical Summary
The challenge in forming insulating layers for printed wiring boards is the deterioration of thickness uniformity and insulation reliability due to resin flow during vacuum pressing, which can lead to poor embedding of circuit board wiring and increased roughness on metal foils, affecting insulation reliability.
A resin sheet with a metal foil support having an arithmetic mean roughness greater than 300 nm and a resin composition layer containing inorganic filler with a specific surface area of 10 m²/g, along with dynamic viscoelasticity properties, is used to form insulating layers through vacuum pressing, ensuring uniformity and embeddability.
The solution provides a cured product with excellent insulating layer thickness uniformity, embeddability, and improved insulation reliability, enhancing the performance of printed wiring boards and semiconductor devices.
Smart Images

Figure 0007615892000001 
Figure 0007615892000002 
Figure 0007615892000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin sheet, and further to a printed wiring board, a semiconductor device, and a method for producing a printed wiring board, which are obtained by using the resin sheet. [Background technology]
[0002] In the manufacture of printed wiring boards, an insulating layer is formed by laminating and curing a prepreg onto a circuit board using a vacuum press process, as described, for example, in US Pat. No. 5,399,363. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-57352 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0004] With the recent trend toward miniaturization of printed wiring boards, etc., there is a demand for using a resin composition layer of a resin sheet instead of a prepreg in order to make the insulating layer thinner. When forming an insulating layer with a resin composition layer of a resin sheet, there is a method of laminating and curing a resin composition layer on a circuit board by a vacuum lamination method, and a method of laminating and curing a resin composition layer on a circuit board by a vacuum press treatment.
[0005] When forming an insulating layer by vacuum press processing using a resin composition layer of a resin sheet, the pressure applied to the resin composition layer of the resin sheet during lamination is higher in the vacuum press processing than in the vacuum lamination method, and the uniformity of the thickness of the insulating layer may deteriorate due to resin flow (exudation of resin) in the resin composition layer, resulting in deterioration of the insulation reliability. On the other hand, if the viscosity of the resin is increased to suppress the resin flow, the insulating layer may not be able to embed the wiring of the circuit board, and the embedding property may be reduced, resulting in poor insulation. In addition, when the support of the resin sheet has a metal foil with high roughness, the thickness of the insulating layer at the location with high roughness is likely to be thin, resulting in a significant deterioration of the insulation reliability.
[0006] An object of the present invention is to provide a resin sheet capable of giving a cured product having excellent insulating layer thickness uniformity, embeddability, and insulation reliability; a printed wiring board and a semiconductor device formed using the resin sheet; and a method for producing a printed wiring board. [Means for solving the problem]
[0007] As a result of intensive research into the above-mentioned problems, the present inventors have discovered a method for manufacturing a support including a metal foil having an arithmetic average roughness (Ra) of more than 300 nm on the surface that is bonded to a resin composition layer, and a metal foil having a specific surface area of 10 m2 or more and provided on the support. 2 The inventors have found that the above-mentioned problems can be solved by forming an insulating layer by vacuum press treatment using a resin sheet comprising a resin composition layer containing an inorganic filler of at least 1.0 / g, and wherein, in dynamic viscoelasticity measurement of the resin composition layer from 60°C to 200°C, the maximum value of tan δ at 100°C or higher is 1.0 or more and 2.0 or less, and have thus completed the present invention.
[0008] That is, the present invention includes the following. [1] A resin sheet for forming an insulating layer using a vacuum press process, A support and a resin composition layer provided on the support, the support has a metal foil having an arithmetic average roughness (Ra) of more than 300 nm on the surface that is bonded to the resin composition layer; The resin composition layer (A) has a specific surface area of 10 m 2 / g or more of inorganic filler, A resin sheet, in which, in dynamic viscoelasticity measurement of a resin composition layer from 60° C. to 200° C., the maximum value of tan δ at 100° C. or higher is 1.0 or higher and 2.0 or lower. [2] The resin sheet according to [1], wherein the resin composition layer has a thickness of 30 μm or less. [3] The resin sheet according to [1] or [2], wherein the resin composition layer contains any one of an active ester resin, a maleimide resin, and a vinyl resin. [4] The resin sheet according to any one of [1] to [3], wherein the content of the component (A) is 73 mass % or less, when the total amount of non-volatile components in the resin composition layer is 100 mass %. [5] The resin sheet according to any one of [1] to [4], wherein the metal foil includes a copper foil. [6] The resin sheet according to any one of [1] to [5], wherein the support has a thickness of 9 μm or more. [7] A printed wiring board comprising an insulating layer made of a cured product of the resin composition layer of the resin sheet according to any one of [1] to [6]. [8] A semiconductor device comprising the printed wiring board according to [7]. [9] (I) a step of laminating the resin sheet according to any one of [1] to [6] on an inner layer substrate by vacuum pressing; (II) a step of thermally curing the resin composition layer to form an insulating layer; A method for manufacturing a printed wiring board, comprising: Effect of the Invention
[0009] According to the present invention, it is possible to provide a resin sheet which can give a cured product having excellent insulating layer thickness uniformity, embeddability, and insulation reliability; a printed wiring board and a semiconductor device formed using the resin sheet; and a method for manufacturing a printed wiring board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below with reference to preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.
[0011] [Resin sheet] The resin sheet of the present invention is a resin sheet for forming an insulating layer using a vacuum press treatment. The resin sheet comprises a support including a metal foil having an arithmetic mean roughness (Ra) of more than 300 nm on the surface that is bonded to a resin composition layer, and (A) a metal foil having a specific surface area of 10 m2 provided on the support. 2 / g or more of an inorganic filler, and in dynamic viscoelasticity measurement of the resin composition layer at 60°C to 200°C, the maximum value of tan δ at 100°C or higher is 1.0 or more and 2.0 or less.
[0012] As described above, when forming an insulating layer using a resin sheet (resin composition layer), the pressure applied to the resin sheet (resin composition layer) during lamination is higher in the vacuum press process than in the conventional vacuum lamination method, and the thickness of the insulating layer may not be uniform due to resin flow. On the other hand, if the viscosity of the resin composition layer is increased to suppress the exudation of the resin, the embeddability may be reduced and the insulation may be poor. The present inventor has found that the maximum value of tan δ (tan δ is the ratio E'' / E' of the storage modulus E' (GPa) and the loss modulus E'' (Pa) in a specific temperature range in the dynamic viscoelasticity of the resin composition layer is related to the uniformity of the thickness of the insulating layer, the embeddability, and the insulation reliability. The present inventor has also found that the maximum value of tan δ can be adjusted by adjusting the amount of residual solvent in the resin composition layer in addition to the specific surface area of the inorganic filler in the resin composition layer, and as a result, it is possible to obtain a cured product having excellent uniformity of the thickness of the insulating layer, embeddability, and insulation reliability.
[0013] Each layer constituting the resin sheet will be described in detail below.
[0014] <Support> In the resin sheet of the present invention, the support has a metal foil having an arithmetic mean roughness (Ra) of more than 300 nm on the support surface on which the resin composition layer is provided. Usually, the support surface having the arithmetic mean roughness (Ra) is the surface of the metal foil, and the surface of this metal foil is in contact with the resin composition layer. This allows the conductor layer described later to be formed from the support.
[0015] The arithmetic mean roughness (Ra) of the support surface on which the resin composition layer is provided is more than 300 nm, preferably 350 nm or more, more preferably 400 nm or more, and even more preferably 500 nm or more, from the viewpoint of improving adhesion with the resin composition layer. The upper limit is not particularly limited, but is preferably 1000 nm or less, more preferably 900 nm or less, and even more preferably 800 nm or less. The arithmetic mean roughness (Ra) is a value measured in accordance with ISO 25178, and can be measured using a non-contact surface roughness meter.
[0016] The ten-point average roughness (Rz) of the support surface on which the resin composition layer is provided is preferably more than 7000 nm, more preferably 8000 nm or more, and even more preferably 9000 nm or more, from the viewpoint of improving adhesion with the resin composition layer. The upper limit is not particularly limited, but is preferably 30000 nm or less, more preferably 20000 nm or less, and even more preferably 10000 nm or less. The ten-point average roughness (Rz) is a value measured in accordance with ISO 25178, and can be measured using a non-contact surface roughness meter.
[0017] The arithmetic mean roughness (Ra) and ten-point mean roughness (Rz) of the support surface can be adjusted to fall within the above ranges by, for example, etching or polishing the support surface.
[0018] The support has a metal foil, and is preferably a metal foil. From the viewpoint of obtaining the effect of the present invention remarkably, the thickness of the support is preferably 9 μm or more, more preferably 10 μm or more, and even more preferably 11 μm or more. The upper limit is not particularly limited, but is preferably 30 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less. The metal foil may have a single layer structure or a multi-layer structure. When the metal foil has a multi-layer structure, it is preferable that the thickness of the entire metal foil is in this range, and the thickness of the ultra-thin metal foil may be, for example, in the range of 0.1 μm to 10 μm.
[0019] Examples of the metal foil include copper foil and aluminum foil, and copper foil is preferred. The copper foil may be a foil made of a single metal such as copper, or may be a foil made of an alloy of copper and another metal (such as tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).
[0020] The metal foil may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. Examples of multi-layer metal foils include metal foils containing a carrier metal foil and an ultra-thin metal foil bonded to the carrier metal foil. Such multi-layer metal foils may include a release layer between the carrier metal foil and the ultra-thin metal foil that allows the ultra-thin metal foil to be peeled off from the carrier metal foil. The release layer is not particularly limited as long as it can peel off the ultra-thin metal foil from the carrier metal foil, and examples of the release layer include an alloy layer of an element selected from the group consisting of Cr, Ni, Co, Fe, Mo, Ti, W, and P; an organic coating, and the like. When a multi-layer metal foil is used as the support, the resin composition layer is provided on the ultra-thin metal foil.
[0021] The method for producing the metal foil is not particularly limited, but it can be produced by known methods such as electrolysis and rolling.
[0022] The support may be provided with any layer other than the metal foil in combination with the metal foil. In this case, from the viewpoint of allowing the metal foil and the resin composition layer to be in direct contact with each other, it is preferable that the any layer is provided on the opposite side of the metal foil to the resin composition layer. Here, the metal foil and the resin composition layer being in "direct" contact with each other means that there is no other layer between the metal foil and the resin composition layer. Among them, it is preferable that there is no any layer, and therefore it is preferable that the support is provided with only the metal foil.
[0023] The support may be a commercially available product, such as "HLP foil" and "JXUT-III foil" manufactured by JX Nippon Mining & Metals Corporation, "Microthin MT-Ex copper foil" and "TP-III foil" manufactured by Mitsui Mining & Smelting Co., Ltd., and "MW-G" manufactured by Mitsui Mining & Smelting Co., Ltd.
[0024] <Resin composition layer> In the resin sheet of the present invention, the resin composition layer provided on the support has (A) a specific surface area of 10 m 2 / g or more of an inorganic filler.
[0025] The resin composition layer may further contain an optional component in combination with the component (A). The optional components include, for example, an epoxy resin (B), a curing agent (C), a radical polymerizable compound (D), a thermoplastic resin (E), a curing accelerator (F), a polymerization initiator (G), and other additives (H). Each component contained in the resin composition layer will be described in detail below.
[0026] -(A) Specific surface area is 10m 2 / g or more inorganic filler The resin composition layer contains, as the component (A), (A) a polymer having a specific surface area of 10 m 2 The resin composition layer containing the component (A) contains an inorganic filler having a filler density of at least 1000 g / g. By using a resin composition layer containing the component (A), it is possible to improve embedding properties and uniformity in the thickness of the insulating layer.
[0027] The specific surface area of component (A) is set to 10 m from the viewpoint of improving embeddability and suppressing thickness variations caused by resin seepage to improve the uniformity of the thickness of the insulating layer. 2 / g or more, preferably 15m 2 / g or more, more preferably 20m 2 / g or more, more preferably 25m 2 / g or more. There is no particular upper limit, but it is preferably 60m 2 / g or less, 50m 2 / g or less or 40m 2 The specific surface area is determined by adsorbing nitrogen gas onto the surface of a sample using a BET fully automatic specific surface area measuring device (Macsorb HM-1210 manufactured by Mountec Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.
[0028] The average particle size of component (A) is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more, from the viewpoint of improving embeddability and suppressing thickness variations due to resin flow and improving the uniformity of the thickness of the insulating layer, and is preferably 5 μm or less, more preferably 4 μm or less, and even more preferably 3 μm or less.
[0029] The average particle size of component (A) can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, a particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample can be prepared by weighing 100 mg of inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing the mixture by ultrasonic waves for 10 minutes. The measurement sample is measured using a laser diffraction particle size distribution measuring device with blue and red light wavelengths as the light source, and the particle size distribution of component (A) on a volume basis is measured using a flow cell method, and the average particle size can be calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.
[0030] As the material of component (A), an inorganic compound is used. Examples of the material of component (A) include silica, alumina, aluminosilicate, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, calcium carbonate and silica are preferred, and silica is particularly preferred. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, as the silica, spherical silica is preferred. The component (A) may be used alone or in combination of two or more types.
[0031] Examples of commercially available products of component (A) include "UFP-30" and "ASFP-20" manufactured by Denka; "SP60-05", "SP507-05", and "SPH516-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs; "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation; and "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs.
[0032] From the viewpoint of improving moisture resistance and dispersibility, it is preferable that the (A) component is treated with a surface treatment agent. Examples of the surface treatment agent include vinylsilane coupling agents, (meth)acrylic coupling agents, fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, and titanate coupling agents. Among them, aminosilane coupling agents are preferable from the viewpoint of obtaining the effects of the present invention significantly. Moreover, the surface treatment agent may be used alone or in any combination of two or more types.
[0033] Commercially available surface treatment agents include, for example, Shin-Etsu Chemical Co., Ltd.'s "KBM1003" (vinyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM503" (3-methacryloxypropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), ... Examples of such silane coupling agents include Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).
[0034] The degree of surface treatment with the surface treatment agent is preferably within a predetermined range from the viewpoint of improving the dispersibility of the inorganic filler. Specifically, 100 parts by mass of the inorganic filler is preferably surface-treated with 0.2 parts by mass to 5 parts by mass of the surface treatment agent, more preferably 0.2 parts by mass to 3 parts by mass, and even more preferably 0.3 parts by mass to 2 parts by mass.
[0035] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of suppressing an increase in the melt viscosity of the resin varnish and the melt viscosity in the form of a sheet, it is more preferable that the content is 1 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:
[0036] The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of the inorganic filler can be measured using a carbon analyzer. The carbon analyzer that can be used is the "EMIA-320V" manufactured by Horiba, Ltd.
[0037] From the viewpoint of adjusting the maximum value of tan δ to an appropriate range, the content of the (A) component is preferably 73% by mass or less, more preferably 72% by mass or less, even more preferably 71% by mass or less, 70% by mass or less, 69% by mass or less, or 68% by mass or less, and is preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more, when the nonvolatile components in the resin composition layer are taken as 100% by mass, unless otherwise specified. In the present invention, the content of each component in the resin composition layer is a value when the nonvolatile components in the resin composition layer are taken as 100% by mass.
[0038] -(B) Epoxy resin- The resin composition layer may contain an epoxy resin (B) as the component (B). The epoxy resin (B) may be used alone or in combination of two or more kinds.
[0039] Examples of the epoxy resin (B) include bixylenol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl ester type epoxy resin, glycidylcyclohexane type epoxy resin, cresol novolac type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, epoxy resin having a butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, spiro ring-containing epoxy resin, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, naphthylene ether type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin, and phenolphthalimidine type epoxy resin. The epoxy resin may be used alone or in combination of two or more kinds.
[0040] The resin composition layer preferably contains, as component (B), an epoxy resin having two or more epoxy groups in one molecule. From the viewpoint of significantly obtaining the desired effects of the present invention, the ratio of the epoxy resin having two or more epoxy groups in one molecule to 100% by mass of the non-volatile components of the thermosetting resin is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0041] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition layer may contain only a liquid epoxy resin or only a solid epoxy resin as a thermosetting resin, but it is preferable to contain a combination of a liquid epoxy resin and a solid epoxy resin.
[0042] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.
[0043] Preferred liquid epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, glycidyl amine type epoxy resins, and epoxy resins having a butadiene structure, glycidyl cyclohexane type epoxy resins, and phenolphthalimidine type epoxy resins, with glycidyl cyclohexane type epoxy resins being more preferred.
[0044] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "Epicoat 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "630" and "630LSD" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation. ); "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Corporation; "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) manufactured by Daicel Corporation; "PB-3600" (epoxy resin having a butadiene structure) manufactured by Daicel Corporation; "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd. These may be used alone or in combination of two or more types.
[0045] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.
[0046] As the solid epoxy resin, bixylenol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, and tetraphenylethane type epoxy resin are preferred, and bixylenol type epoxy resin and naphthalene type epoxy resin are more preferred.
[0047] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin), "HP-4700", "HP-4710" (naphthalene type tetrafunctional epoxy resin), "N-690" (cresol novolac type epoxy resin), "N-695" (cresol novolac type epoxy resin), "HP-7200", "HP-7200HH", "HP-7200H" (dicyclopentadiene type epoxy resin), "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000", "HP6000L" (naphthylene ether type epoxy resin), and "EPPN-502H" (trisphenol type epoxy resin), "NC7000L" (naphthol novolac type epoxy resin), "NC3000H", "NC3000", "NC3000L" manufactured by Nippon Kayaku Co., Ltd. Examples of epoxy resins include "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthalene type epoxy resin) and "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YL6121" (biphenyl type epoxy resin), "YX4000HK" (bixylenol type epoxy resin), and "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin), "YL7800" (fluorene type epoxy resin), "jER1010" (solid bisphenol A type epoxy resin), and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; and "WHR-991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. These may be used alone or in combination of two or more.
[0048] When a liquid epoxy resin and a solid epoxy resin are used in combination as component (B), the ratio by mass (liquid epoxy resin:solid epoxy resin) is preferably 1:0.1 to 1:20, more preferably 1:0.3 to 1:10, and particularly preferably 1:0.5 to 1:5. When the ratio by mass of the liquid epoxy resin and the solid epoxy resin is within this range, the desired effects of the present invention can be significantly obtained.
[0049] The epoxy equivalent of the (B) component is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. Within this range, a cured product having sufficient crosslink density of the cured product of the resin composition layer can be obtained. The epoxy equivalent is the mass of an epoxy resin containing one equivalent of an epoxy group. This epoxy equivalent can be measured according to JIS K7236.
[0050] From the viewpoint of significantly obtaining the desired effects of the present invention, the weight average molecular weight (Mw) of the component (B) is preferably 100 to 5000, more preferably 250 to 3000, and further preferably 400 to 1500. The weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0051] The content of the (B) component is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer, from the viewpoint of obtaining a cured product exhibiting good mechanical strength and insulation reliability. The upper limit of the epoxy resin content is preferably 35% by mass or less, more preferably 30% by mass or less, and particularly preferably 25% by mass or less, from the viewpoint of significantly obtaining the desired effects of the present invention.
[0052] -(C) Hardener- The resin composition layer may contain a (C) curing agent as the (C) component. The (C) curing agent usually has a function of reacting with the (B) component to cure the resin composition. The (C) curing agent may be used alone or in combination of two or more kinds.
[0053] As the (C) curing agent, a curing agent having low polarity is preferable. Examples of the (C) curing agent include active ester resins, phenol resins, naphthol resins, benzoxazine resins, cyanate ester resins, carbodiimide resins, amine resins, and acid anhydride resins. Among them, from the viewpoint of obtaining the effects of the present invention remarkably, it is preferable to contain an active ester resin.
[0054] As the active ester resin, a resin having one or more active ester groups in one molecule can be used. Among them, as the active ester resin, a resin having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferable. The active ester resin is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester resin obtained from a carboxylic acid compound and a hydroxy compound is preferable, and an active ester resin obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferable.
[0055] Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid.
[0056] Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0057] Preferred specific examples of the active ester resin include active ester resins containing a dicyclopentadiene-type diphenol structure, active ester resins containing a naphthalene structure, active ester resins containing an acetylated product of phenol novolac, and active ester resins containing a benzoylated product of phenol novolac. Among them, active ester resins containing a naphthalene structure and active ester resins containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.
[0058] Commercially available active ester resins include those containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" (manufactured by DIC Corporation); those containing a naphthalene structure, such as "EXB9416-70BK", "EXB-8150-65T", and "HP-B-8151-62T" (manufactured by DIC Corporation); and those containing an acetylated product of phenol novolac. Examples of active ester resins that include benzoyl phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Corporation); active ester resins that include benzoyl phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Corporation); active ester resins that are acetylated phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Corporation); and active ester resins that are benzoyl phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), and "YLH1048" (manufactured by Mitsubishi Chemical Corporation).
[0059] As the phenolic resin and naphtholic resin, those having a novolac structure are preferred from the viewpoint of heat resistance and water resistance, and from the viewpoint of adhesion to the conductor layer, nitrogen-containing phenolic curing agents are preferred, and triazine skeleton-containing phenolic resins are more preferred.
[0060] Specific examples of phenol-based resins and naphthol-based resins include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemical Industry Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", "SN375", and "SN395" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA-3018-50P", and "EXB-9500" manufactured by DIC Corporation.
[0061] Specific examples of benzoxazine resins include "JBZ-OD100" (benzoxazine ring equivalent: 218), "JBZ-OP100D" (benzoxazine ring equivalent: 218), and "ODA-BOZ" (benzoxazine ring equivalent: 218) manufactured by JFE Chemical Corporation; "Pd" (benzoxazine ring equivalent: 217) and "Fa" (benzoxazine ring equivalent: 217) manufactured by Shikoku Chemical Industry Co., Ltd.; and "HFB2006M" (benzoxazine ring equivalent: 432) manufactured by Showa Polymer Co., Ltd.
[0062] Examples of cyanate ester resins include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester resins include "PT30", "PT30S" and "PT60" (phenol novolac type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230", "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), and "BADCy" (bisphenol A dicyanate), all of which are manufactured by Lonza Japan.
[0063] Specific examples of carbodiimide resins include Carbodilite (registered trademark) V-03 (carbodiimide group equivalent: 216, V-05 (carbodiimide group equivalent: 216), V-07 (carbodiimide group equivalent: 200); V-09 (carbodiimide group equivalent: 200), all manufactured by Nisshinbo Chemical Inc.; and Stavaxol (registered trademark) P (carbodiimide group equivalent: 302), all manufactured by Rhein Chemie.
[0064] Examples of the amine-based resin include resins having one or more amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, and aromatic amines. Among these, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based resin is preferably a primary amine or a secondary amine, and more preferably a primary amine. Specific examples of the amine-based curing agent include 4,4'-methylenebis(2,6-dimethylaniline), diphenyldiaminosulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)- ... Examples of suitable amine resins include bis(4-aminophenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, and bis(4-(3-aminophenoxy)phenyl)sulfone. Commercially available amine resins may be used, such as "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.
[0065] Examples of the acid anhydride resin include resins having one or more acid anhydride groups in one molecule. Specific examples of the acid anhydride resin include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, and benzophenonetetracarboxylic dianhydride. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid.
[0066] When the resin composition layer contains an epoxy resin and a curing agent, the ratio of the amount of the epoxy resin to all the curing agents is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.05 to 1:3, and even more preferably 1:0.1 to 1:2, in terms of the ratio of [total number of epoxy groups in the epoxy resin]:[total number of reactive groups in the curing agent]. Here, the "number of epoxy groups in the epoxy resin" refers to the total value obtained by dividing the mass of the non-volatile components of the epoxy resin present in the first resin composition by the epoxy equivalent. In addition, the "number of active groups in the curing agent" refers to the total value obtained by dividing the mass of the non-volatile components of the curing agent present in the first resin composition by the active group equivalent. By setting the ratio of the amount of the epoxy resin to the curing agent as a thermosetting resin within this range, a cured product having excellent flexibility can be obtained.
[0067] In order to obtain the effects of the present invention prominently, the content of the (C) curing agent is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, relative to 100% by mass of the non-volatile components in the resin composition layer, and is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less.
[0068] -(D) Radical polymerizable compound- The resin composition layer may contain a radically polymerizable compound as component (D). The component (D) may be used alone or in combination of two or more kinds.
[0069] In one embodiment, the radical polymerizable compound (D) is a radical polymerizable compound having an ethylenically unsaturated bond. The radical polymerizable compound (D) is not particularly limited, but may have a radical polymerizable group such as an unsaturated hydrocarbon group such as an allyl group, a 3-cyclohexenyl group, a 3-cyclopentenyl group, a p-vinylphenyl group, a m-vinylphenyl group, or an o-vinylphenyl group; an α,β-unsaturated carbonyl group such as an acryloyl group, a methacryloyl group, or a maleimide group (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl group). The radical polymerizable compound (D) preferably has two or more radical polymerizable groups.
[0070] The radically polymerizable compound (D) may be, for example, a maleimide resin, a vinyl resin, a (meth)acrylic resin, an allyl resin, etc. Among these, the component (D) preferably contains either a maleimide resin or a vinyl resin, and more preferably contains both a maleimide resin and a vinyl resin.
[0071] The maleimide resin (maleimide radically polymerizable compound) is, for example, a compound having one or more, preferably two or more maleimide groups. The maleimide resin may be an aliphatic maleimide compound containing an aliphatic amine skeleton, or an aromatic maleimide compound containing an aromatic amine skeleton. Commercially available products include, for example, "SLK-2600" manufactured by Shin-Etsu Chemical Co., Ltd., "BMI-1500", "BMI-1700", "BMI-3000J", "BMI-689", and "BMI-2500" (dimer diamine structure-containing maleimide compounds) manufactured by Designer Molecules, Inc., "BMI-6100" (aromatic maleimide compound) manufactured by Designer Molecules, "MIR-5000-60T" and "MIR-3000-70MT" (biphenylaralkyl-type maleimide compounds) manufactured by Nippon Kayaku Co., Ltd., "BMI-70" and "BMI-80" manufactured by K.I. Chemical Industry Co., Ltd., and "BMI-2300" and "BMI-TMH" manufactured by Daiwa Kasei Kogyo Co., Ltd. In addition, as the maleimide-based resin, a maleimide-based resin (an indane ring skeleton-containing maleimide compound) disclosed in the Japan Institute of Invention and Innovation's Technical Journal Publication No. 2020-500211 may be used.
[0072] Vinyl resins (vinyl radical polymerizable compounds (also called styrene radical polymerizable compounds)) are compounds having, for example, one or more, preferably two or more vinyl groups directly bonded to an aromatic carbon atom. Examples of vinyl resins include low molecular weight (molecular weight less than 1000) styrene compounds such as divinylbenzene, 2,4-divinyltoluene, 2,6-divinylnaphthalene, 1,4-divinylnaphthalene, 4,4'-divinylbiphenyl, 1,2-bis(4-vinylphenyl)ethane, 2,2-bis(4-vinylphenyl)propane, and bis(4-vinylphenyl)ether; and high molecular weight (molecular weight 1000 or more) styrene compounds such as vinylbenzyl-modified polyphenylene ether resins and styrene-divinylbenzene copolymers. Examples of commercially available styrene-based radically polymerizable compounds include "ODV-XET(X03)", "ODV-XET(X04)", and "ODV-XET(X05)" (styrene-divinylbenzene copolymers) manufactured by Nippon Steel Chemical & Material Co., Ltd., and "OPE-2St 1200" and "OPE-2St 2200" (vinylbenzyl-modified polyphenylene ether resins) manufactured by Mitsubishi Gas Chemical Co., Inc.
[0073] The (meth)acrylic resin ((meth)acrylic radical polymerizable compound) is, for example, a compound having one or more, preferably two or more, acryloyl groups and / or methacryloyl groups. Examples of the (meth)acrylic resin include cyclohexane-1,4-dimethanol di(meth)acrylate, cyclohexane-1,3-dimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and the like. Di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and other low molecular weight (molecular weight less than 1000) aliphatic (meth)acrylic acid ester compounds; dioxane glycol di(meth)acrylate, 3,6-dioxa-1,8-octanediol di(meth)acrylate, Examples of the ether-containing (meth)acrylic acid ester compounds include low molecular weight (molecular weight less than 1000) ether-containing (meth)acrylic acid ester compounds such as acrylate, 3,6,9-trioxaundecane-1,11-diol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, ethoxylated bisphenol A di(meth)acrylate, and propoxylated bisphenol A di(meth)acrylate; low molecular weight (molecular weight less than 1000) isocyanurate-containing (meth)acrylic acid ester compounds such as tris(3-hydroxypropyl)isocyanurate tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and ethoxylated isocyanuric acid tri(meth)acrylate; and high molecular weight (molecular weight 1000 or more) acrylic acid ester compounds such as (meth)acrylic-modified polyphenylene ether resin.Commercially available (meth)acrylic resins include, for example, "A-DOG" (dioxane glycol diacrylate) manufactured by Shin-Nakamura Chemical Co., Ltd., "DCP-A" (tricyclodecane dimethanol diacrylate) and "DCP" (tricyclodecane dimethanol dimethacrylate) manufactured by Kyoeisha Chemical Co., Ltd., "KAYARAD R-684" (tricyclodecane dimethanol diacrylate) and "KAYARAD R-604" (dioxane glycol diacrylate) manufactured by Nippon Kayaku Co., Ltd., and "SA9000" and "SA9000-111" (methacrylic-modified polyphenylene ether) manufactured by SABIC Innovative Plastics.
[0074] The allyl resin (allyl radically polymerizable compound) is, for example, a compound having one or more, preferably two or more, allyl groups. Examples of allyl resins include aromatic carboxylic acid allyl ester compounds such as diallyl diphenate, triallyl trimellitate, diallyl phthalate, diallyl isophthalate, diallyl terephthalate, diallyl 2,6-naphthalenedicarboxylate, and diallyl 2,3-naphthalenecarboxylate; isocyanuric acid allyl ester compounds such as 1,3,5-triallyl isocyanurate and 1,3-diallyl-5-glycidyl isocyanurate; epoxy-containing aromatic allyl compounds such as 2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane; benzoxazine-containing aromatic allyl compounds such as bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane; ether-containing aromatic allyl compounds such as 1,3,5-triallyl ether benzene; and allyl silane compounds such as diallyl diphenyl silane. Commercially available allyl resins include "TAIC" (1,3,5-triallyl isocyanurate) manufactured by Nippon Kasei Chemical Industry Co., Ltd., "DAD" (diallyl diphenate) manufactured by Nisshoku Techno Fine Chemical Co., Ltd., "TRIAM-705" (triallyl trimellitate) manufactured by Wako Pure Chemical Industries, Ltd., trade name "DAND" (2,3-naphthalene carboxylate diallyl) manufactured by Nippon Distillation Industry Co., Ltd., "ALP-d" (bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane) manufactured by Shikoku Kasei Corporation, "RE-810NM" (2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane) manufactured by Nippon Kayaku Co., Ltd., and "DA-MGIC" (1,3-diallyl-5-glycidyl isocyanurate) manufactured by Shikoku Kasei Corporation.
[0075] The ethylenically unsaturated bond equivalent of the component (D) is preferably 20 g / eq. to 3000 g / eq., more preferably 50 g / eq. to 2500 g / eq., further preferably 70 g / eq. to 2000 g / eq., and particularly preferably 90 g / eq. to 1500 g / eq. The ethylenically unsaturated bond equivalent is the mass of the radical polymerizable compound per equivalent of the ethylenically unsaturated bond.
[0076] The weight average molecular weight (Mw) of the component (D) is preferably 40,000 or less, more preferably 10,000 or less, even more preferably 5,000 or less, and particularly preferably 3,000 or less. The lower limit is not particularly limited, but may be, for example, 150 or more.
[0077] From the viewpoint of obtaining the effects of the present invention remarkably, the content of the (D) component is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer. From the viewpoint of obtaining the effects of the present invention remarkably, the upper limit of the content of the (D) component is preferably 40% by mass or less, more preferably 35% by mass or less, and particularly preferably 30% by mass or less.
[0078] As a component to be contained in the resin composition layer, it is preferable to use a material having low polarity from the viewpoint of improving the resin flow and insulation reliability. Examples of such a material having low polarity include active ester resin, maleimide resin, vinyl resin, etc. Therefore, a preferred embodiment of the resin sheet is preferably a combination of component (A) with at least one of (B) epoxy resin, (C) curing agent, and (D) radical polymerizable compound, and more preferably a combination of component (A) with at least one of active ester resin, maleimide resin, and vinyl resin.
[0079] -(E) Thermoplastic resin- The resin composition layer may contain a thermoplastic resin (E) as the component (E). By including the component (E) in the resin composition layer, it is possible to obtain a cured product exhibiting good mechanical strength. The component (E) may be used alone or in combination of two or more kinds.
[0080] From the viewpoint of significantly obtaining the effects of the present invention, the weight average molecular weight (Mn) of the component (E) is preferably at least 5000, more preferably at least 8000, particularly preferably at least 10000, and is preferably at most 100000, more preferably at most 80000, particularly preferably at most 50000. The weight average molecular weight of the component (E) is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0081] As the (E) component, a high molecular weight component having a weight average molecular weight within the above range can be used. Examples of such components include thermoplastic resins such as polyimide resins, phenoxy resins, polyvinyl acetal resins, polyolefin resins, polyamideimide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, and polyester resins; and elastomers. Among them, from the viewpoint of obtaining the effects of the present invention significantly, the (E) component is preferably at least one selected from polyimide resins, elastomers, and phenoxy resins.
[0082] The polyimide resin may include a polyimide resin containing a structural unit represented by the following formula (e1) (hereinafter, also referred to as "structural unit (e1)") (hereinafter, may be referred to as "first polyimide resin"). In the first polyimide resin, the number of structural units (e1) is 1 or more, and is not particularly limited, but may be 100 or less, 50 or less, or 30 or less. When there are a plurality of structural units (e1), the structural units (e1) may be linked to each other as repeating units, or may not be linked to each other. When not linked to each other, it is preferable that the plurality of structural units (e1) have another structural unit (for example, a structural unit represented by the formula (e2) described later) between them.
[0083] The structural unit (e1) is represented by the following formula (e1). [ka] [In formula (e1), R1 is a tetravalent group represented by the following formula (e1-1): R2 is a divalent group represented by the following formula (e1-2).
[0084] [ka] (In formula (e1-1), Ar 11 , Ar 12 , Ar 13 and Ar 14 each independently represents an aromatic ring which may have a substituent, L 11 , L 12 and L 13 each independently represents a divalent linking group, nc1 represents an integer equal to or greater than 0.)
[0085] [ka] (In formula (e1-2), Ar 21 , Ar 22 , Ar 23 and Ar 24 each independently represents an aromatic ring which may have a substituent, L 21 , L 22 and L 23 each independently represents a divalent linking group, nc2 represents an integer equal to or greater than 1. )]
[0086] In formula (e1-1), Ar 11 , Ar 12 , Ar 13 and Ar 14 The aromatic ring represented by (hereinafter also referred to as "aromatic ring C") is preferably an aromatic ring having 6 to 100 carbon atoms, more preferably 6 to 50 carbon atoms, still more preferably 6 to 100 carbon atoms, and even more preferably 6 to 50 carbon atoms. Therefore, in a preferred embodiment, in formula (e1-1), Ar 11 , Ar 12 , Ar 13 and Ar14 are each independently an aromatic carbocyclic ring having 6 to 14 carbon atoms which may have a substituent. In this specification, the term "aromatic ring" means a ring according to the Huckel rule in which the number of electrons contained in the π electron system on the ring is 4n+2 (n is a natural number), and includes a monocyclic aromatic ring and a fused aromatic ring in which two or more monocyclic aromatic rings are fused together. The aromatic ring may be a carbocyclic ring or a heterocyclic ring. Examples of the aromatic ring include monocyclic aromatic rings such as a benzene ring, a furan ring, a thiophene ring, a pyrrole ring, a pyrazole ring, an oxazole ring, an isoxazole ring, a thiazole ring, an imidazole ring, a pyridine ring, a pyridazine ring, a pyrimidine ring, and a pyrazine ring; fused rings in which two or more monocyclic aromatic rings are fused, such as a naphthalene ring, an anthracene ring, a benzofuran ring, an isobenzofuran ring, an indole ring, an isoindole ring, a benzothiophene ring, a benzimidazole ring, an indazole ring, a benzoxazole ring, a benzisoxazole ring, a benzothiazole ring, a quinoline ring, an isoquinoline ring, a quinoxaline ring, an acridine ring, a quinazoline ring, a cinnoline ring, and a phthalazine ring; and fused rings in which one or more monocyclic aromatic rings are fused to one or more monocyclic non-aromatic rings, such as an indane ring, a fluorene ring, and a tetralin ring. Among these, an aromatic carbon ring having 6 to 14 carbon atoms is preferred, and a benzene ring is more preferred.
[0087] In formula (e1-1), Ar 11 , Ar 12 , Ar 13 and Ar 14 When represents an aromatic ring having a substituent, the number of the substituent is not limited. Such a substituent (hereinafter also referred to as "substituent S") may be, independently of one another, a halogen atom, an alkyl group, a cycloalkyl group, an alkoxy group, a cycloalkyloxy group, an aryl group, an aryloxy group, an arylalkyl group, an arylalkoxy group, a monovalent heterocyclic group, an alkylidene group, an amino group, a silyl group, an acyl group, an acyloxy group, a carboxy group, a sulfo group, a cyano group, a nitro group, a hydroxy group, a mercapto group, and an oxo group.
[0088] In formula (e1-1), L 11 , L12 and L 13 The divalent linking group represented by is preferably a divalent group consisting of one or more (for example, 1 to 3000, 1 to 1000, 1 to 100, 1 to 50) skeletal atoms selected from carbon atoms, oxygen atoms, nitrogen atoms, sulfur atoms, and silicon atoms. Examples of the divalent linking group include -SO2-, -CO-, -COO-, -O-, -S-, -O-C6H4-O- (wherein -C6H4- represents a phenylene group), -O-C6H4-C(CH3)2-C6H4-O-, -COO-(CH2) q -OCO- (wherein q represents an integer of 1 to 20), -COO-H2C-HC(-OC(=O)-CH3)-CH2-OCO-, an alkylene group, an alkenylene group, an alkynylene group, an arylene group, a heteroarylene group, -C(=O)-, -C(=O)-O-, -NR 0 - (where R 0 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; and -C(=O)-NR 0 -. As the alkylene group, an alkylene group having 1 to 10 carbon atoms is preferable, an alkylene group having 1 to 6 carbon atoms is more preferable, and an alkylene group having 1 to 5 carbon atoms or an alkylene group having 1 to 4 carbon atoms is even more preferable. As the alkylene group, for example, a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, a hexylene group, a dimethylmethylene group, etc. are mentioned, and a dimethylmethylene group is preferable. As the alkenylene group, an alkenylene group having 2 to 10 carbon atoms is preferable, an alkenylene group having 2 to 6 carbon atoms is more preferable, and an alkenylene group having 2 to 5 carbon atoms is even more preferable. As the arylene group and the heteroarylene group, an arylene group or a heteroarylene group having 6 to 20 carbon atoms is preferable, and an arylene group or a heteroarylene group having 6 to 10 carbon atoms is even more preferable. The above-mentioned alkyl group, alkylene group, alkenylene group, alkynylene group, arylene group, and heteroarylene group may further have a substituent. Examples of the substituent are the same as the examples of the substituent S. 11 , L 12 and L 13 It is preferable that the divalent linking group represented by does not contain an aromatic ring. 11A divalent linking group represented by 13 and the divalent linking group represented by 11 A divalent linking group represented by 12 In a preferred embodiment, in formula (e1-1), L 11 and L 13 is -O- and L 12 In a more preferred embodiment, in formula (e1-1), Ar 11 , Ar 12 , Ar 13 and Ar 14 are each independently an aromatic carbocyclic ring having 6 to 14 carbon atoms which may have a substituent, and in formula (e1-1), L 11 and L 13 is -O- and L 12 In a further preferred embodiment, in formula (e1-1), L 11 and L 13 is -O- and L 12 is a dimethylmethylene group.
[0089] In formula (e1-2), Ar 21 , Ar 22 , Ar 23 and Ar 24 Examples of the aromatic ring represented by and the substituent that the aromatic ring may have are the same as the examples of the aromatic ring C and the substituent S, respectively. Therefore, in a preferred embodiment, in formula (e1-2), Ar 21 , Ar 22 , Ar 23 and Ar 24 are each independently an aromatic carbon ring having 6 to 14 carbon atoms which may have a substituent. 21 and L 23 is -O- and L 22 is an alkylene group which may have a substituent, and in a more preferred embodiment, in formula (e1-2), 21 , Ar 22 , Ar 23 and Ar 24are each independently an aromatic carbocyclic ring having 6 to 14 carbon atoms which may have a substituent, and in formula (e1-2), L 21 and L 23 is -O- and L 22 In a further preferred embodiment, in formula (e1-2), L 21 and L 23 is -O- and L 22 In a particularly preferred embodiment, in formula (e1-1), Ar 11 , Ar 12 , Ar 13 and Ar 14 are each independently an aromatic carbocyclic ring having 6 to 14 carbon atoms which may have a substituent, and in formula (e1-2), Ar 21 , Ar 22 , Ar 23 and Ar 24 are each independently an aromatic carbon ring having 6 to 14 carbon atoms which may have a substituent. 11 and L 13 is -O- and L 12 is an alkylene group which may have a substituent, and in formula (e1-2), L 21 and L 23 is -O- and L 22 In a more particularly preferred embodiment, in formula (e1-1), Ar 11 , Ar 12 , Ar 13 and Ar 14 each independently represents an aromatic carbocyclic ring having 6 to 14 carbon atoms which may have a substituent, and in formula (e1-2), Ar 21 , Ar 22 , Ar 23 and Ar 24 each independently represents an aromatic carbocyclic ring having 6 to 14 carbon atoms which may have a substituent, and in formula (e1-1), L 11 and L 13 is -O- and L 12is an alkylene group which may have a substituent, and in formula (e1-2), L 21 and L 23 is -O- and L 22 is an alkylene group which may have a substituent.
[0090] In formula (e1-1), nc1 preferably represents an integer of 1 or more. The upper limit of the integer represented by nc1 is not particularly limited, but may be, for example, 50, 40, 30, or 20.
[0091] In formula (e1-2), nc2 preferably represents an integer of 2 or more. The upper limit of the integer represented by nc2 is not particularly limited, and may be, for example, 60, 50, 40, or 30. In an embodiment, the integer represented by nc2 in formula (e1-1) is greater than the integer represented by nc1 and less than nc1+5. In a specific embodiment, in formula (e1-1), nc1 is 1 and nc2 is 2.
[0092] The structural unit (e1) can be obtained, for example, by a known method for producing a polyimide resin, typically by polymerizing a monomer composition containing a tetracarboxylic dianhydride and a diamine compound to form an imidized product, or by polymerizing a monomer composition containing a tetracarboxylic dianhydride and a diisocyanate compound to form an imidized product. It is acceptable for the first polyimide resin to partially contain a polyamic acid structure that may be generated during the imidization process.
[0093] The structural unit (e1) in the above specific embodiment can be obtained, for example, by reacting 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (a compound represented by the following formula (eI); hereinafter, also referred to as "BPADA") with 4,4'-[1,4-phenylenebis[(1-methylethylidene)-4,1-phenyleneoxy]]bisbenzenamine (a compound represented by the following formula (eII); hereinafter, also referred to as "BPPAN"). That is, in the structural unit (e1), R1 is a skeleton derived from BPADA, and R2 is a skeleton derived from BPPAN.
[0094] [ka]
[0095] [ka]
[0096] The first polyimide resin may further include a structural unit represented by the following formula (e2) (hereinafter, also referred to as "structural unit (e2)"). Thus, in one embodiment, the first polyimide resin is a resin further including a structural unit represented by the following formula (e2). In the first polyimide resin, the number of structural units (e2) is 0 or more, and is not particularly limited, but may be 100 or less, 50 or less, or 30 or less. The structural unit (e2) may be linked to the group R2 of the structural unit (e1) through the nitrogen atom of the imide group, or may not be linked to the structural unit (e1). When there are a plurality of structural units (e2), the structural units (e2) may be linked to each other as a repeating unit, or may not be linked to each other. When not linked to each other, it is preferable that the plurality of structural units (e2) have another structural unit (e1, for example) between them.
[0097] The structural unit (e2) is represented by the following formula (e2). [ka] (In formula (e2), R3 represents a tetravalent aliphatic group which may have a substituent or a tetravalent aromatic group which may have a substituent; R4 represents a divalent aliphatic group which may have a substituent or a divalent aromatic group which may have a substituent, provided that when R3 is the same as R1, R4 is different from R2, and when R4 is the same as R2, R3 is different from R1.
[0098] In formula (e2), the tetravalent aliphatic group represented by R3 contains at least a carbon atom, and is preferably a tetravalent group consisting of one or more (e.g., 1 to 3000, 1 to 1000, 1 to 100, 1 to 50) skeletal atoms selected from carbon atoms, oxygen atoms, nitrogen atoms, sulfur atoms, and silicon atoms. In formula (e2), the tetravalent aliphatic group represented by R3 is more preferably a tetravalent aliphatic group having 1 to 100 carbon atoms, and further preferably 1 to 50 carbon atoms. In formula (e2), when R3 represents a tetravalent aliphatic group having a substituent, examples of the substituent are the same as the examples of the substituent S.
[0099] In formula (e2), the tetravalent aromatic group represented by R3 is preferably a tetravalent aromatic group having 6 to 100 carbon atoms, more preferably 6 to 50 carbon atoms, and even more preferably a tetravalent aromatic hydrocarbon group having 6 to 100 carbon atoms, and even more preferably 6 to 50 carbon atoms. The aromatic group contains at least an aromatic ring. Examples of the aromatic ring contained in the aromatic group include Ar 11 , Ar 12 , Ar 13 and Ar 14 In the formula (e2), when R3 represents a tetravalent aromatic group having a substituent, examples of the substituent are the same as the examples of the substituent S.
[0100] The tetravalent aromatic group represented by R3 may be a group obtained by removing two acid anhydride groups from a tetracarboxylic dianhydride having an aromatic group which may have a substituent. The aromatic group includes at least an aromatic ring. Examples of the aromatic ring contained in the aromatic group are the same as the examples of the aromatic ring C. When the aromatic group has a substituent, examples of the substituent are the same as the examples of the substituent S. Specific examples of tetracarboxylic dianhydrides having an aromatic group which may have a substituent include BPADA, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride.
[0101] In formula (e2), the divalent aliphatic group represented by R4 contains at least a carbon atom, and is preferably a divalent group consisting of one or more (e.g., 1 to 3000, 1 to 1000, 1 to 100, 1 to 50) skeletal atoms selected from carbon atoms, oxygen atoms, nitrogen atoms, sulfur atoms, and silicon atoms. In formula (e2), the divalent aliphatic group represented by R4 is more preferably a divalent aliphatic group having 1 to 100 carbon atoms, and even more preferably a divalent aliphatic group having 1 to 50 carbon atoms. In formula (e2), when R4 represents a divalent aliphatic group having a substituent, examples of the substituent are the same as the examples of the substituent S, and are, for example, an alkyl group having 1 to 6 carbon atoms. Therefore, in an embodiment, R4 is a divalent aliphatic group which may have a substituent, and one of the substituents is an alkyl group having 1 to 6 carbon atoms. In a specific embodiment, R4 is a divalent aliphatic group which may have a substituent, and is a divalent group obtained by removing two amino groups from isophoronediamine.
[0102] When R4 represents a divalent aliphatic group which may have a substituent, it may be a group obtained by removing two amino groups from a diamine compound having an aliphatic group which may have a substituent selected from 1,2-diaminoethane, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine. These diamine compounds are characterized in that the aliphatic group is linear.
[0103] When R4 represents a divalent aliphatic group which may have a substituent, it may be a group obtained by removing two amino groups from a diamine compound having an aliphatic group which may have a substituent selected from 1,2-diaminopropane, 1,2-diamino-2-methylpropane, 1,3-diamino-2-methylpropane, 1,3-diamino-2,2-dimethylpropane, 1,3-diaminopentane, and 1,5-diamino-2-methylpentane. These diamine compounds are characterized in that the aliphatic group is branched.
[0104] When R4 represents a divalent aliphatic group which may have a substituent, examples thereof include 5-amino-1,3,3-trimethylcyclohexanemethylamine (isophoronediamine), 1,4-diaminocyclohexane, 1,3-diaminocyclohexane, 1,4-cyclohexanebis(methylamine), 1,3-cyclohexanebis(methylamine), 4,4'-diaminodicyclohexylmethane, bis(4-amino-3-methylcyclohexyl)methane, 3(4),8(9)-bis(aminomethyl)tricyclo[5.2.1.0 2,6 ]decane, 2,5(6)-bis(aminomethyl)bicyclo[2.2.1]heptane, 1,3-diaminoadamantane, 3,3'-diamino-1,1'-biadamantyl, and 1,6-diaminoadamantane, from which two amino groups have been removed. These diamine compounds are characterized in that the aliphatic group contains an alicyclic carbon ring.
[0105] In formula (e2), the divalent aromatic group represented by R4 is preferably a divalent aromatic group having 6 to 100 carbon atoms, more preferably 6 to 50 carbon atoms, and even more preferably a divalent aromatic hydrocarbon group having 6 to 100 carbon atoms, still more preferably 6 to 50 carbon atoms. The aromatic group contains at least an aromatic ring. Examples of the aromatic ring contained in the aromatic group are the same as the examples of the aromatic ring C. In formula (e2), when R4 represents a divalent aromatic group having a substituent, examples of the substituent are the same as the examples of the substituent S.
[0106] When R4 represents a divalent aromatic group which may have a substituent, it may be a group obtained by removing two amino groups from a diamine compound having an aromatic group which may have a substituent selected from 4,4'-diaminodiphenyl ether, 1,4-phenylenediamine, and 2,2-bis[4-(4-aminophenoxy)phenyl]propane.
[0107] However, when R3 is the same as R1, R4 is different from R2, and when R4 is the same as R2, R3 is different from R1. In some embodiments, R3 is the same as R1. That is, the structural unit (e2) is different from the structural unit (e1).
[0108] The structural unit (e2) can be obtained, for example, according to a known method for producing a polyimide resin. The structural unit (e2) in the above specific embodiment can be obtained, for example, by reacting BPADA with isophoronediamine. That is, R3 in the structural unit (e2) is a skeleton derived from BPADA, and R4 is a skeleton derived from isophoronediamine. When R3 is the same as R1, R3 and R1 are skeletons derived from BPADA. It is acceptable for the first polyimide resin to partially contain a polyamic acid structure that may be generated during the imidization process.
[0109] The terminal structure of the first polyimide resin is not particularly limited as long as it has the structural unit (e1). For example, the terminal structure of the polyimide resin may be an acid anhydride group derived from the raw material compound of the polyimide resin (for example, an acid such as BPADA, an amine compound such as BPPAN), or a carboxyl group or an amino group. When the raw material compound further contains maleic anhydride, the terminal structure of the polyimide resin may be a maleimide group.
[0110] Glass transition temperature Tg of polyimide resin (c) (°C) is preferably 140°C or higher, more preferably 145°C or higher, even more preferably 150°C or higher, even more preferably 160°C or higher, and particularly preferably 170°C or higher. The upper limit is not particularly limited, but may be 300°C or lower. (c) The temperature (°C) can be measured using a Rigaku TMA device at a temperature rise rate of 5°C / min from 25°C to 250°C.
[0111] The content (percentage) of the structural unit (e1) in the polyimide resin is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 20% by mass or more, even more preferably 30% by mass or more, and particularly preferably 40% by mass or more, from the viewpoint of obtaining the effects of the present invention remarkably. The content (percentage) of the structural unit (e1) in the polyimide resin may be, for example, 98% by mass or less, 95% by mass or less, 90% by mass or less, or 85% by mass or less. Here, the content (percentage) of the structural unit (e1) can be calculated from the ratio of the charged amount (parts by mass) of each material used to synthesize the polyimide resin, or alternatively, the molecular weight of the polyimide resin and the formula weight of the structural unit (e1) may be specified, and the content (percentage) of the structural unit (e1) may be calculated as the ratio to the molecular weight. When the polyimide resin is a polymer, it is preferable that the content (percentage) of the structural unit (e1) estimated from the degree of polymerization is within the above range.
[0112] When the polyimide resin further contains the structural unit (e2), the content (percentage) of the structural unit (e2) is allowed to be 0% by mass (i.e., no structural unit (e2) is contained), and the upper limit is not limited as long as the effect of the present invention is not excessively impaired. Therefore, the content (percentage) of the structural unit (e2) in the polyimide resin may be, for example, 1% by mass or more, 5% by mass or more, 10% by mass or more, 20% by mass or more, or 30% by mass or more, 95% by mass or less, 90% by mass or less, 80% by mass or less, 70% by mass or less, or 60% by mass or less. Here, the content (percentage) of the structural unit (e2) is calculated in the same manner as the content (percentage) of the structural unit (e1). When the polyimide resin is a polymer, it is preferable that the content (percentage) of the structural unit (e2) estimated from the degree of polymerization is within the above range.
[0113] The weight average molecular weight (Mw) of the polyimide resin is usually 1,000 or more, preferably 1,00 to 10,000, more preferably 1,000 to 5,000, and further preferably 1,000 to 3,000. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.
[0114] Another embodiment of the polyimide resin is a resin containing a first skeleton derived from BPADA and a second skeleton derived from BPPAN (hereinafter, sometimes referred to as a "second polyimide resin"). The material of the first skeleton is not limited to BPADA, so long as it is the same skeleton as the skeleton derived from BPADA. The material of the second skeleton is not limited to BPPAN, so long as it is the same skeleton as the skeleton derived from BPPAN. In the second polyimide resin, the number of first skeletons is 1 or more, and is not particularly limited, but may be 100 or less, 50 or less, or 30 or less. In the second polyimide resin, the number of second skeletons is 1 or more, and is not particularly limited, but may be 100 or less, 50 or less, or 30 or less.
[0115] The above-mentioned first and second skeletons can be derived from, for example, a known method for producing a polyimide resin, typically a method for imidizing a monomer composition containing a tetracarboxylic dianhydride and a diamine compound by polymerization. The first and second skeletons can also be derived from a method for imidizing a monomer composition containing a tetracarboxylic dianhydride and a diisocyanate compound by polymerization. Therefore, the second polyimide resin can contain the structural unit (e1) contained in the first polyimide resin. It is acceptable for the second polyimide resin to contain a portion of a polyamic acid structure that can be generated during the imidization process.
[0116] The second polyimide resin may further include a third skeleton different from the second skeleton. The third skeleton is derived from one or more diamine compounds selected from the group consisting of diamine compounds having an aliphatic group which may have a substituent and diamine compounds having an aromatic group which may have a substituent. Therefore, in one embodiment, the second polyimide resin is a resin further including a third skeleton different from the second skeleton, and the third skeleton is derived from one or more diamine compounds selected from the group consisting of diamine compounds having an aliphatic group which may have a substituent and diamine compounds having an aromatic group which may have a substituent. In the second specific polyimide resin, the number of the third skeleton is 0 or more, and is not particularly limited, but may be 100 or less, 50 or less, or 30 or less.
[0117] When the diamine compound is a diamine compound having an aliphatic group, the aliphatic group contains at least a carbon atom, and is preferably a group consisting of one or more (e.g., 1 to 3000, 1 to 1000, 1 to 100, 1 to 50) skeletal atoms selected from carbon atoms, oxygen atoms, nitrogen atoms, sulfur atoms, and silicon atoms, more preferably an aliphatic group having 1 to 100 carbon atoms, and further preferably 1 to 50. When the aliphatic group has a substituent, examples of the substituent are the same as the examples of the substituent S.
[0118] When the diamine compound is a diamine compound having an aromatic group, the aromatic group is preferably a tetravalent aromatic group having 6 to 100 carbon atoms, more preferably 6 to 50 carbon atoms, and further preferably a tetravalent aromatic hydrocarbon group having 6 to 100 carbon atoms, even more preferably 6 to 50 carbon atoms. The aromatic group contains at least an aromatic ring. Examples of the aromatic ring contained in the aromatic group are the same as the examples of the aromatic ring C. When the aromatic group has a substituent, examples of the substituent are the same as the examples of the substituent S.
[0119] The third skeleton may be a skeleton derived from a diamine compound having an aliphatic group having an alkyl group having 1 to 6 carbon atoms as a substituent. The third skeleton may also be a skeleton derived from isophoronediamine. Therefore, in an embodiment, the second polyimide resin is a resin further including a skeleton derived from a diamine compound having an aliphatic group having an alkyl group having 1 to 6 carbon atoms as a substituent. A specific example of such a skeleton is a skeleton derived from isophoronediamine. The skeleton derived from isophoronediamine (5-amino-1,3,3-trimethylcyclohexanemethylamine) may be a skeleton derived from 5-isocyanato-1-(isocyanatomethyl)-1,3,3-trimethylcyclohexane.
[0120] The third skeleton may be derived from one or more skeletons selected from diamine compounds having an aromatic group which may have a substituent, such as 4,4'-diaminodiphenyl ether, 1,4-phenylenediamine, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, etc. Such a third skeleton is characterized by having an aromatic group.
[0121] The third skeleton may be derived from one or more diamine compounds having an aliphatic group which may have a substituent, such as 1,2-diaminoethane, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, etc. Such a third skeleton is characterized in that the aliphatic group is linear.
[0122] The third skeleton may be derived from one or more diamine compounds having an aliphatic group which may have a substituent, such as 1,2-diaminopropane, 1,2-diamino-2-methylpropane, 1,3-diamino-2-methylpropane, 1,3-diamino-2,2-dimethylpropane, 1,3-diaminopentane, 1,5-diamino-2-methylpentane, etc. Such a third skeleton is characterized in that the aliphatic group is branched.
[0123] The third skeleton is 5-amino-1,3,3-trimethylcyclohexanemethylamine (isophoronediamine), 1,4-diaminocyclohexane, 1,3-diaminocyclohexane, 1,4-cyclohexanebis(methylamine), 1,3-cyclohexanebis(methylamine), 4,4'-diaminodicyclohexylmethane, bis(4-amino-3-methylcyclohexyl)methane, 3(4),8(9)-bis(aminomethyl)tricyclo[5.2.1.0]. 2,6 ]decane, 2,5(6)-bis(aminomethyl)bicyclo[2.2.1]heptane, 1,3-diaminoadamantane, 3,3'-diamino-1,1'-biadamantyl, 1,6-diaminoadamantane, etc. The third skeleton may be derived from one or more diamine compounds having an aliphatic group which may have a substituent, such as 1,2-dimethyl-2,4-dimethylphenylacetamide, ...
[0124] The above-mentioned third skeleton may be generated in the second polyimide resin by, for example, polymerizing a monomer composition containing a tetracarboxylic dianhydride that can be the material of the first skeleton and a diamine compound that can be the material of the second skeleton to form an imidization, by adding a diamine compound or a diisocyanate compound that can be the material of the third skeleton to the monomer composition or by sequentially mixing them during polymerization. Therefore, the second polyimide resin may contain the structural unit (e2) that the first polyimide resin may contain. It is acceptable for the second polyimide resin to partially contain a polyamic acid structure that can be generated during the imidization process.
[0125] The second polyimide resin may further include a fourth skeleton different from the first skeleton. The fourth skeleton is derived from one or more acids selected from the group consisting of acids other than BPADA. In the second polyimide resin, the number of the fourth skeletons is 0 or more, and is not particularly limited, but may be 100 or less, 50 or less, or 30 or less.
[0126] Examples of acids other than BPADA include tetracarboxylic dianhydrides having an aromatic group which may have a substituent. The aromatic group is preferably an aromatic group having 6 to 100 carbon atoms, more preferably 6 to 50 carbon atoms, and even more preferably an aromatic hydrocarbon group having 6 to 100 carbon atoms, still more preferably 6 to 50 carbon atoms. The aromatic group contains at least an aromatic ring. Examples of the aromatic ring contained in the aromatic group are the same as the examples of the aromatic ring C. When the aromatic group has a substituent, examples of the substituent are the same as the examples of the substituent S. Specific examples of tetracarboxylic dianhydrides having an aromatic group which may have a substituent include pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride.
[0127] Glass transition temperature Tg of the second polyimide resin (c’)(°C) is preferably 140°C or higher, more preferably 145°C or higher, even more preferably 150°C or higher, even more preferably 160°C or higher, and particularly preferably 170°C or higher. The upper limit is not particularly limited, but may be 300°C or lower. (c’) The temperature (° C.) can be measured in the same manner as in the first polyimide resin.
[0128] From the viewpoint of enhancing the intended effect of the present invention, the total content ratio (percentage) of the first skeleton and the second skeleton in the second polyimide resin is preferably 4% by mass or more, more preferably 9% by mass or more, even more preferably 19% by mass or more, even more preferably 29% by mass or more, and particularly preferably 39% by mass or more. The total content ratio (percentage) of the first skeleton and the second skeleton may be, for example, 97% by mass or less, 94% by mass or less, 89% by mass or less, or 84% by mass or less. Here, the total content ratio (percentage) of the first skeleton and the second skeleton can be calculated from the ratio of the charged amount (parts by mass) contributing to the reaction of each material used to synthesize the second polyimide resin, and instead, the molecular weight of the second polyimide resin and the formula weight of the first skeleton and the second skeleton incorporated in the resin may be specified, and the total formula weight of the first skeleton and the second skeleton may be calculated as the ratio to the molecular weight. When the second polyimide resin is a polymer, it is preferable that the total content (percentage) of the first skeleton and the second skeleton estimated from the degree of polymerization falls within the above range.
[0129] When the second polyimide resin is a resin further containing a third skeleton, the content ratio (percentage) of the third skeleton is allowed to be 0 mass% (i.e., no third skeleton), and the upper limit is not limited as long as the effect of the present invention is not excessively impaired. Therefore, the content ratio (percentage) of the third skeleton in the second polyimide resin may be, for example, more than 0 mass%, 4 mass% or more, 9 mass% or more, 19 mass% or more, or 29 mass% or more, 94 mass% or less, 89 mass% or less, 79 mass% or less, 69 mass% or less, or 59 mass% or less. Here, the content ratio (percentage) of the third skeleton is calculated in the same manner as the content ratio (percentage) of the first skeleton and the content ratio (percentage) of the second skeleton. When the second polyimide resin is a polymer, it is preferable that the content ratio (percentage) of the third skeleton estimated from the degree of polymerization is within the above-mentioned range. When the second polyimide resin further contains a fourth skeleton, the content ratio (percentage) of the fourth skeleton is the same as the content ratio (percentage) of the third skeleton.
[0130] The second polyimide resin is not particularly limited in its terminal structure as long as it is a resin containing a first skeleton derived from BPADA and a second skeleton derived from BPPAN. For example, the terminal structure of the second polyimide resin may be an acid anhydride group, a carboxyl group, or an amino group derived from the raw material compound of the second polyimide resin (e.g., an acid such as BPADA, or an amine compound such as BPPAN). When the raw material compound further contains maleic anhydride, the terminal structure of the second polyimide resin may be a maleimide group.
[0131] The weight average molecular weight (Mw) of the second polyimide resin is usually 1,000 or more, preferably 1,00 to 10,000, more preferably 1,000 to 5,000, and further preferably 1,000 to 3,000. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.
[0132] Another embodiment of the polyimide resin is a resin obtained by polymerizing and imidizing a monomer composition containing at least BPADA and BPPAN (hereinafter, sometimes referred to as "third polyimide resin"). The polymerization and imidization are not particularly limited, but are usually carried out in a solvent. In the polymerization, the blending ratio of BPADA and BPPAN is preferably determined according to the total number of functional groups possessed by each component, and in one embodiment, the ratio of the total number of amino groups possessed by BPPAN in the monomer composition to the total number of acid anhydride groups possessed by BPADA is within the range of 0.1:1 to 10:1, preferably within the range of 0.5:1 to 10:1, more preferably within the range of 0.8:1 to 10:1, and even more preferably within the range of 0.9:1 to 10:1. The imidization is not particularly limited, but is usually carried out in a solvent by heating in the absence of a catalyst, by heating in the presence of a catalyst, or in the presence of a catalyst at room temperature. From the viewpoint of enhancing the intended effect of the present invention, the imidization is preferably carried out by heating in the absence of a catalyst. The third polyimide resin may be any of a random copolymer, an alternating copolymer, and a block copolymer. The third polyimide resin is not limited to the above-mentioned polymerization and imidization method. It is acceptable for the third polyimide resin to contain a part of a polyamic acid structure that may be generated during the imidization process. The third polyimide resin thus obtained contains the above-mentioned structural unit (e1) contained in the first polyimide resin. The third polyimide resin thus obtained also contains the above-mentioned first skeleton and second skeleton contained in the second polyimide resin.
[0133] The monomer composition may contain, as other monomers, an acid other than BPADA and / or a diamine compound other than BPPAN, and other monomers may be added during the reaction.
[0134] Examples of acids other than BPADA include tetracarboxylic dianhydrides having an aromatic group which may have a substituent. The aromatic group is preferably a tetravalent aromatic group having 6 to 100 carbon atoms, more preferably 6 to 50 carbon atoms, and even more preferably a tetravalent aromatic hydrocarbon group having 6 to 100 carbon atoms, still more preferably 6 to 50 carbon atoms. The aromatic group contains at least an aromatic ring. Examples of the aromatic ring contained in the aromatic group are the same as the examples of the aromatic ring C. When the aromatic group has a substituent, examples of the substituent are the same as the examples of the substituent S. Specific examples of tetracarboxylic dianhydrides having an aromatic group which may have a substituent include pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride. The molar ratio of the content of an acid other than BPADA to the content of BPADA in the monomer composition is not particularly limited, but may be, for example, 0.5 or less, 0.4 or less, or 0.3 or less.
[0135] In one embodiment, the monomer composition further contains one or more diamine compounds selected from the group consisting of diamine compounds having an aliphatic group which may have a substituent and diamine compounds having an aromatic group which may have a substituent. The molar ratio of the content of the diamine compounds other than BPPAN to the content of BPPAN in the monomer composition is not particularly limited, but may be, for example, 0.5 or less, 0.4 or less, or 0.3 or less.
[0136] When the diamine compound is a diamine compound having an aliphatic group, the aliphatic group contains at least a carbon atom, and is preferably a group consisting of one or more (e.g., 1 to 3000, 1 to 1000, 1 to 100, 1 to 50) skeletal atoms selected from carbon atoms, oxygen atoms, nitrogen atoms, sulfur atoms, and silicon atoms, more preferably an aliphatic group having 1 to 100 carbon atoms, and further preferably 1 to 50. When the aliphatic group has a substituent, examples of the substituent are the same as the examples of the substituent S.
[0137] When the diamine compound is a diamine compound having an aromatic group, the aromatic group is preferably a tetravalent aromatic group having 6 to 100 carbon atoms, more preferably 6 to 50 carbon atoms, and even more preferably a tetravalent aromatic hydrocarbon group having 6 to 100 carbon atoms, even more preferably 6 to 50 carbon atoms. The aromatic group contains at least an aromatic ring. Examples of the aromatic ring contained in the aromatic group are the same as the examples of the aromatic ring C. When the aromatic group has a substituent, examples of the substituent are the same as the examples of the substituent S. When the diamine compound is a diamine compound having an aromatic group which may have a substituent, examples thereof include one or more selected from diamine compounds having an aromatic group such as 4,4'-diaminodiphenyl ether, 1,4-phenylenediamine, and 2,2-bis[4-(4-aminophenoxy)phenyl]propane.
[0138] When the diamine compound is a diamine compound having an aliphatic group which may have a substituent, a first example thereof may be a skeleton derived from one or more selected from diamine compounds having an aliphatic group which may have a substituent, such as 1,2-diaminoethane, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, etc. The diamine compound according to this first example is characterized in that the aliphatic group is linear.
[0139] When the diamine compound is a diamine compound having an aliphatic group which may have a substituent, a second example thereof may be a skeleton derived from one or more selected from diamine compounds having an aliphatic group which may have a substituent, such as 1,2-diaminopropane, 1,2-diamino-2-methylpropane, 1,3-diamino-2-methylpropane, 1,3-diamino-2,2-dimethylpropane, 1,3-diaminopentane, 1,5-diamino-2-methylpentane, etc. The diamine compound according to this second example is characterized in that the aliphatic group is branched.
[0140] When the diamine compound is a diamine compound having an aliphatic group which may have a substituent, examples of the third example include 5-amino-1,3,3-trimethylcyclohexanemethylamine (isophoronediamine), 1,4-diaminocyclohexane, 1,3-diaminocyclohexane, 1,4-cyclohexanebis(methylamine), 1,3-cyclohexanebis(methylamine), 4,4'-diaminodicyclohexylmethane, bis(4-amino-3-methylcyclohexyl)methane, 3(4),8(9)-bis(aminomethyl)tricyclo[5.2.1.0] 2,6 The skeleton may be derived from one or more selected from diamine compounds having an aliphatic group which may have a substituent, such as 2,5(6)-bis(aminomethyl)bicyclo[2.2.1]heptane, 1,3-diaminoadamantane, 3,3'-diamino-1,1'-biadamantyl, and 1,6-diaminoadamantane. The diamine compound according to the third example is characterized in that the aliphatic group contains an alicyclic carbon ring.
[0141] Based on the above, in one embodiment, the monomer composition further contains a diamine compound having an aliphatic group having an alkyl group having 1 to 6 carbon atoms as a substituent. In a specific embodiment, the monomer composition further contains isophoronediamine.
[0142] The third polyimide resin is not particularly limited in its terminal structure as long as it is a resin obtained by polymerizing the monomer composition and imidizing it. For example, the terminal structure of the third polyimide resin may be an acid anhydride group, a carboxyl group, or an amino group derived from a raw material compound (e.g., an acid such as BPADA, an amine compound such as BPPAN) contained in the monomer composition of the third polyimide resin. When the raw material compound further contains maleic anhydride, the terminal structure of the third polyimide resin may be a maleimide group.
[0143] The weight average molecular weight (Mw) of the third polyimide resin is 1,000 or more, preferably 1,00 to 10,000, more preferably 1,000 to 5,000, and further preferably 1,000 to 3,000. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.
[0144] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. The phenoxy resin is preferably a phenoxy resin having a weight average molecular weight of 30,000 or more.
[0145] Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.
[0146] The polyamide-imide resin is a resin having an amide-imide structure. From the viewpoint of compatibility with other components in the resin composition layer, it is preferable to use a polyamide-imide resin having an alicyclic structure in the molecular structure, a polyamide-imide resin having a siloxane structure described in JP-A-05-112760, a polyamide-imide resin having a bulky branched chain structure, a polyamide-imide resin made from an asymmetric monomer, a polyamide-imide resin having a multi-branched structure, or the like.
[0147] Among these, from the viewpoint that the polyamideimide resin has an isocyanuric ring structure, which improves compatibility and dispersibility with resin varnish, (i) polyamideimide resins having an isocyanuric ring structure in their molecular structure (i.e., polyamideimide resins having an isocyanuric ring structure and an imide skeleton or an amide skeleton), (ii) polyamideimide resins having an isocyanuric ring structure and an alicyclic structure in their molecular structure (i.e., polyamideimide resins having an isocyanuric ring structure, an alicyclic structure, and an imide skeleton or an amide skeleton), and (iii) polyamideimide resins having repeating units containing an isocyanuric ring structure and an alicyclic structure (i.e., polyamideimide resins having repeating units containing an isocyanuric ring structure, an alicyclic structure, and an imide skeleton or an amide skeleton).
[0148] A preferred embodiment of the polyamideimide resins (i) to (iii) includes (1) a carboxylic acid group-containing branched polyamideimide obtained by reacting an isocyanuric ring-containing polyisocyanate compound derived from an alicyclic diisocyanate with an acid anhydride of a polycarboxylic acid having three or more carboxyl groups (hereinafter, the compound may be referred to as "(compound E-e1)"); (2) a carboxylic acid group-containing branched polymerizable polyamideimide obtained by reacting compound (E-e1) with a compound having one epoxy group and one or more radically polymerizable unsaturated groups (hereinafter, the compound may be referred to as "compound (E-e2)"); or (3) a carboxylic acid group-containing branched polymerizable polyamideimide obtained by reacting a compound having one hydroxyl group and one or more radically polymerizable unsaturated groups with a remaining isocyanate group in the synthesis process of compound (E-e1) (hereinafter, the compound may be referred to as "compound (E-e3)").
[0149] Specific examples of the compound (E-e1) include compounds represented by the following general formula (I): The repeating unit in the compound represented by the general formula (I) is referred to as repeating unit (I-1). [ka] (In the formula, w represents 0 to 15.)
[0150] An example of the compound (E-e2) is a compound (II) having a structure (I-2) in which GMA (glycidyl methacrylate) is added to any part of the carboxyl groups and / or terminal carboxyl groups of the repeating unit (I-1) in the general formula (I). [ka] (In the formula, R 40 represents a residue in formula (I).
[0151] The proportion of GMA modification of carboxyl groups is preferably 0.3 mol% or more, more preferably 0.5 mol% or more, even more preferably 0.7 mol% or more, or 0.9 mol% or more, based on the number of moles of carboxyl groups in compound (E-e1). The upper limit is preferably 50 mol% or less, more preferably 40 mol% or less, even more preferably 30 mol% or less, or 20 mol% or less.
[0152] An example of the compound (E-e3) is a compound (III) having a structure (I-3) in which any part of the repeating unit (I-1) and / or the terminal imide group in the above formula (I) is an isocyanate residue to which a hydroxyl group of pentaerythritol triacrylate is added. [ka] (In the formula, R' represents a residue in formula (I).)
[0153] The amount of pentaerythritol triacrylate added is preferably 40 mol% or less, more preferably 38 mol% or less, and even more preferably 35 mol% or less, based on the number of moles of isocyanate groups in the polyisocyanate at the time of charging. On the other hand, from the viewpoint of fully obtaining the effect of the addition, the amount of pentaerythritol triacrylate added is preferably 0.3 mol% or more, more preferably 3 mol% or more, and even more preferably 5 mol% or more, based on the number of moles of isocyanate groups in the polyisocyanate at the time of charging.
[0154] The polyamide-imide resin can be synthesized by various known methods. For the synthesis method of the polyamide-imide resin, for example, the description in paragraphs 0020 to 0030 of WO 2010 / 074197 can be referred to, the contents of which are incorporated herein by reference.
[0155] The polyamide-imide resin may be a commercially available product, such as modified polyamide-imide such as "UNIDIC V-8000" manufactured by DIC Corporation, "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd., and "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.
[0156] From the viewpoint of compatibility with other components in the resin composition layer, the polyester resin preferably has a fluorene structure in its molecular structure, and preferably has, in addition to the fluorene structure, a structural unit derived from a diol and a structural unit derived from a dicarboxylic acid.
[0157] A specific example of the polyester resin is "OKP4HT" manufactured by Osaka Gas Chemicals Co., Ltd.
[0158] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.
[0159] Examples of polyvinyl acetal resins include polyvinyl formal resins and polyvinyl butyral resins, and polyvinyl butyral resins are preferred. Specific examples of polyvinyl acetal resins include S-LEC BH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0160] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.
[0161] The elastomer in component (E) is a resin having flexibility, and is preferably a resin having rubber elasticity or a resin exhibiting rubber elasticity by polymerization with another component. Examples of rubber elasticity include resins exhibiting an elastic modulus of 1 GPa or less when a tensile test is performed at a temperature of 25°C and a humidity of 40% RH according to the Japanese Industrial Standards (JIS K7161). Elastomers are usually amorphous resin components that can be dissolved in organic solvents. One type of elastomer may be used alone, or two or more types may be used in combination at any ratio.
[0162] In one embodiment, the elastomer is preferably a resin having, in the molecule, one or more structures selected from a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, a polycarbonate structure, and a polystyrene structure. "(Meth)acrylate" refers to methacrylate and acrylate.
[0163] In another embodiment, the elastomer is preferably one or more selected from a resin having a glass transition temperature (Tg) of 25° C. or less and a resin that is liquid at 25° C. or less. The glass transition temperature of the resin having a glass transition temperature (Tg) of 25° C. or less is preferably 20° C. or less, more preferably 15° C. or less. The lower limit of the glass transition temperature is not particularly limited, but can usually be −15° C. or more. The resin that is liquid at 25° C. is preferably a resin that is liquid at 20° C. or less, more preferably a resin that is liquid at 15° C. or less. The glass transition temperature can be measured by DSC (differential scanning calorimetry).
[0164] The elastomer may be, for example, a resin containing a polybutadiene structure. The polybutadiene structure may be contained in the main chain or in the side chain. The polybutadiene structure may be partially or entirely hydrogenated. A resin containing a polybutadiene structure may be called a "polybutadiene resin." Specific examples of polybutadiene resins include "Ricon 130MA8", "Ricon 130MA13", "Ricon 130MA20", "Ricon 131MA5", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", and "Ricon 184MA6" (polybutadiene containing an acid anhydride group) manufactured by Cray Valley Corporation; "GQ-1000" (polybutadiene having hydroxyl groups and carboxyl groups introduced therein), "G-1000", "G-2000", and "G-3000" (polybutadiene having hydroxyl groups at both ends), "GI-1000", "GI-2000", and "GI-3000" (polybutadiene having hydrogenated hydroxyl groups at both ends) manufactured by Nippon Soda Co., Ltd.; and "FCA-061L" (hydrogenated polybutadiene skeleton epoxy resin) manufactured by Nagase ChemteX Corporation. Specific examples of polybutadiene resins include hydroxyl-terminated polybutadiene, linear polyimides made from diisocyanate compounds and tetrabasic acid anhydrides (polyimides described in JP 2006-37083 A and WO 2008 / 153208 A), and phenolic hydroxyl-containing butadiene. The content of the butadiene structure in the polyimide resin is preferably 60% by mass to 95% by mass, more preferably 75% by mass to 85% by mass. For details of the polyimide resin, refer to the descriptions in JP 2006-37083 A and WO 2008 / 153208 A, the contents of which are incorporated herein by reference.
[0165] Examples of elastomers include resins containing a poly(meth)acrylate structure. Resins containing a poly(meth)acrylate structure are sometimes called "poly(meth)acrylic resins." Specific examples of poly(meth)acrylic resins include Teisan Resin manufactured by Nagase ChemteX Corporation, and ME-2000, W-116.3, W-197C, KG-25, and KG-3000 manufactured by Negami Chemical Industries, Ltd.
[0166] Examples of elastomers include resins containing a polycarbonate structure. Resins containing a polycarbonate structure are sometimes called "polycarbonate resins". Examples of such resins include carbonate resins that do not have a reactive group, hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, urethane group-containing carbonate resins, and epoxy group-containing carbonate resins. The reactive group here refers to a functional group that can react with other components, such as a hydroxyl group, a phenolic hydroxyl group, a carboxyl group, an acid anhydride group, an isocyanate group, a urethane group, and an epoxy group. Specific examples of polycarbonate resins include "FPC0220" and "FPC2136" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002" and "T6001" (polycarbonate diols) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diols) manufactured by Kuraray Co., Ltd. In addition, linear polyimides made from hydroxyl-terminated polycarbonate, diisocyanate compounds, and tetrabasic acid anhydrides can also be used. The content of the carbonate structure in the polyimide resin is preferably 60% by mass to 95% by mass, more preferably 75% by mass to 85% by mass. For details of the polyimide resin, refer to the description in International Publication No. 2016 / 129541, the contents of which are incorporated herein by reference.
[0167] Examples of elastomers include resins containing a polysiloxane structure. Resins containing a polysiloxane structure are sometimes called "siloxane resins." Specific examples of siloxane resins include "SMP-2006," "SMP-2003PGMEA," and "SMP-5005PGMEA" manufactured by Shin-Etsu Silicone Co., Ltd., and linear polyimides made from amine-terminated polysiloxanes and tetrabasic acid anhydrides (see International Publication No. 2010 / 053185, JP 2002-12667 A, JP 2000-319386 A, etc.).
[0168] Examples of the elastomer include resins containing a polyalkylene structure or a polyalkyleneoxy structure. A resin containing a polyalkylene structure may be referred to as an "alkylene resin". A resin containing a polyalkyleneoxy structure may be referred to as an "alkyleneoxy resin". The polyalkyleneoxy structure is preferably a polyalkyleneoxy structure having 2 to 15 carbon atoms, more preferably a polyalkyleneoxy structure having 3 to 10 carbon atoms, and particularly preferably a polyalkyleneoxy structure having 5 to 6 carbon atoms. Specific examples of the alkylene resin and the alkyleneoxy resin include "PTXG-1000" and "PTXG-1800" manufactured by Asahi Kasei Fibers Corporation.
[0169] Examples of elastomers include resins containing a polyisoprene structure. Resins containing a polyisoprene structure are sometimes called "isoprene resins." Specific examples of isoprene resins include "KL-610" and "KL613" manufactured by Kuraray Co., Ltd.
[0170] Examples of elastomers include resins containing a polyisobutylene structure. Resins containing a polyisobutylene structure are sometimes called "isobutylene resins." Specific examples of isobutylene resins include Kaneka Corporation's "SIBSTAR-073T" (styrene-isobutylene-styrene triblock copolymer) and "SIBSTAR-042D" (styrene-isobutylene diblock copolymer).
[0171] An example of the elastomer is a resin containing a polystyrene structure. A resin containing a polystyrene structure is sometimes called a "styrene resin." The styrene resin may be a copolymer containing an arbitrary repeating unit other than the styrene unit in combination with the styrene unit, or may be a hydrogenated polystyrene resin.
[0172] Examples of the optional repeating unit include a repeating unit (conjugated diene unit) having a structure obtained by polymerizing a conjugated diene, and a repeating unit (hydrogenated conjugated diene unit) having a structure obtained by hydrogenating the same. Examples of the conjugated diene include aliphatic conjugated dienes such as butadiene, isoprene, 2,3-dimethylbutadiene, 1,3-pentadiene, and 1,3-hexadiene; and halogenated aliphatic conjugated dienes such as chloroprene. As the conjugated diene, an aliphatic conjugated diene is preferable, and butadiene is more preferable, from the viewpoint of obtaining the effects of the present invention significantly. The conjugated diene may be used alone or in combination of two or more kinds. The polystyrene resin may be a random copolymer or a block copolymer.
[0173] Examples of styrene resins include styrene-butadiene-styrene block copolymers (SBS), styrene-isoprene-styrene block copolymers (SIS), styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), styrene-butadiene-butylene-styrene block copolymers (SBBS), styrene-butadiene diblock copolymers, hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-isoprene block copolymers, hydrogenated styrene-butadiene random copolymers, and styrene-maleic anhydride copolymers. Specific examples of styrene resins include hydrogenated styrene-based thermoplastic elastomers "H1041", "Tuftec H1043", "Tuftec P2000", and "Tuftec MP10" (manufactured by Asahi Kasei Corporation); epoxidized styrene-butadiene thermoplastic elastomers "Epofriend AT501" and "CT310" (manufactured by Daicel Corporation); modified styrene-based elastomers having hydroxyl groups "Septon HG252" (manufactured by Kuraray Co., Ltd.); modified styrene-based elastomers having carboxyl groups "Tuftec N503M", modified styrene-based elastomers having amino groups "Tuftec N501", modified styrene-based elastomers having acid anhydride groups "Tuftec M1913" (manufactured by Asahi Kasei Chemicals Corporation); unmodified styrene-based elastomers "Septon S8104" (manufactured by Kuraray Co., Ltd.); styrene-ethylene / butylene-styrene block copolymers "FG1924" (manufactured by Kraton Corporation), and "EF-40" (manufactured by CRAY VALLEY Co., Ltd.).
[0174] The number average molecular weight (Mn) of the elastomer is preferably 1,000 or more, more preferably 1,500 or more, even more preferably 3,000 or more, particularly preferably 5,000 or more, and is preferably 1,000,000 or less, more preferably 900,000 or less. The number average molecular weight (Mn) can be measured in terms of polystyrene using GPC (gel permeation chromatography).
[0175] From the viewpoint of obtaining a remarkable effect of the present invention, the content of the (E) component is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, based on 100% by mass of the non-volatile components in the resin composition layer.
[0176] -(F) Curing accelerator- The resin composition may contain a curing accelerator (F) as the component (F). Examples of the curing accelerator (F) include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. Amine-based curing accelerators and imidazole-based curing accelerators are preferred, and amine-based curing accelerators are more preferred. The curing accelerator may be used alone or in combination of two or more.
[0177] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, and the like, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.
[0178] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.
[0179] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2, 4-Diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-furan Examples of the imidazole compounds include imidazole compounds such as 2-ethyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred.
[0180] As the imidazole-based curing accelerator, a commercially available product may be used, for example, "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0181] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.
[0182] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0183] From the viewpoint of obtaining the effects of the present invention prominently, the content of the (F) curing accelerator is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and particularly preferably 0.03% by mass or more, when the non-volatile components in the resin composition layer are taken as 100% by mass, and is preferably 3% by mass or less, more preferably 2% by mass or less, and particularly preferably 1% by mass or less.
[0184] -(G) Polymerization initiator- The resin composition layer may contain a polymerization initiator (G) as the component (G). By containing the polymerization initiator (G), the component (D) in particular can be cured.
[0185] The type of polymerization initiator is not particularly limited, and examples thereof include radical generators such as cyclohexanone peroxide, tert-butyl peroxybenzoate, methyl ethyl ketone peroxide, dicumyl peroxide, tert-butyl cumyl peroxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, tert-butyl hydroperoxide, and 2,3-dimethyl-2,3-diphenylbutane. These may be used alone or in combination of two or more.
[0186] The polymerization initiator (G) may be a commercially available product, such as "Perhexine 25B" manufactured by NOF Corporation.
[0187] From the viewpoint of obtaining the effects of the present invention prominently, the content of the (G) polymerization initiator is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, more preferably 0.05% by mass or more, and is preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less, based on 100% by mass of the non-volatile components in the resin composition layer.
[0188] -(H) Other Additives- The resin composition layer may further contain other additives as optional components in addition to the above-mentioned components. Examples of such additives include resin additives such as thickeners, defoamers, leveling agents, and adhesion-imparting agents. These additives may be used alone or in combination of two or more. The content of each additive can be appropriately set by a person skilled in the art.
[0189] The resin composition layer may further contain any solvent as a volatile component. The resin composition used to form the resin composition layer may contain a solvent to adjust the varnish viscosity. Examples of the solvent include organic solvents. However, it is preferable that the resin composition layer does not contain toluene, and when the entire resin composition layer is taken as 100 mass, the content of toluene is preferably 0.1 mass% or less, 0.01 mass% or less, 0.001 mass% or less, or 0.0001 mass% or less.
[0190] Examples of organic solvents include ketones such as methyl ethyl ketone (MEK) and cyclohexanone, aromatic hydrocarbons such as xylene and tetramethylbenzene, glycol ethers such as methyl cellosolve, butyl cellosolve, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether, esters such as ethyl acetate, butyl acetate, butyl cellosolve acetate, carbitol acetate, and ethyl diglycol acetate, aliphatic hydrocarbons such as octane and decane, and petroleum solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. These may be used alone or in combination of two or more.
[0191] From the viewpoint of improving embeddability and uniformity of the thickness of the insulating layer, the melt viscosity of the resin composition layer is adjusted by adjusting the amount of the solvent in the resin composition layer in addition to adjusting the specific surface area of the inorganic filler, so that the maximum value of tan δ is 1.0 or more and 2.0 or less. The amount of the solvent in the resin composition layer (residual solvent amount) is preferably 3 mass% or less, more preferably 2.5 mass% or less, even more preferably 2 mass% or less, even more preferably 1.5 mass% or less, and particularly preferably 1 mass% or less. There is no particular restriction on the lower limit, but it may be 0.0001 mass% or more.
[0192] In dynamic viscoelasticity measurement of the resin composition layer at 60°C to 200°C, the maximum value of tan δ at 100°C or higher is 1.0 or higher, preferably 1.1 or higher, and more preferably 1.3 or higher, from the viewpoint of improving embeddability. Moreover, the maximum value of tan δ is 2.0 or lower, preferably 1.9 or lower, and more preferably 1.8 or lower, from the viewpoint of improving the uniformity of the thickness of the insulating layer. The maximum value of tan δ can be measured according to the method described in the examples below.
[0193] The thickness of the resin composition layer is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer can usually be 5 μm or more, 10 μm or more, etc., from the viewpoint of increasing insulation reliability.
[0194] <Other layers> In one embodiment, the resin sheet may further include other layers as necessary. Examples of such other layers include a protective film provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress adhesion of dirt and scratches on the surface of the resin composition layer.
[0195] <Method of manufacturing resin sheet> The resin sheet can be produced, for example, by preparing a resin varnish by dissolving the resin composition in an organic solvent, applying the resin varnish onto a support using a die coater or the like, and then drying the varnish to form a resin composition layer. The organic solvent may be any of those described above.
[0196] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the organic solvent in the resin varnish, for example, when a resin varnish containing 30 mass % to 60 mass % of organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.
[0197] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0198] <Physical properties and applications of resin sheets> The resin sheet of the present invention is a resin sheet for forming an insulating layer using a vacuum press treatment, and includes a support and a resin composition layer provided on the support, the support having a metal foil having an arithmetic mean roughness (Ra) of more than 300 nm on the surface on the side bonded to the resin composition layer, and the resin composition layer has (A) a specific surface area of 10 m 2 / g or more of an inorganic filler, and in dynamic viscoelasticity measurement of the resin composition layer at 60° C. to 200° C., the maximum value of tan δ at 100° C. or higher is 1.0 or more and 2.0 or less. By forming an insulating layer by a vacuum press treatment using such a resin sheet, it is possible to realize an insulating layer that is excellent in embedding property and uniformity of the insulating layer thickness as well as excellent insulating property.
[0199] The resin composition layer of the resin sheet and the circuit board are laminated by vacuum pressing, and the resin composition layer is thermally cured at 100°C for 30 minutes and then at 200°C for 120 minutes. The cured product of the resin composition layer exhibits excellent embeddability. Therefore, the cured product provides an insulating layer with excellent embeddability. Specifically, the resin composition layer of the resin sheet is laminated on a glass cloth-based epoxy resin double-sided copper-clad laminate (hereinafter referred to as "copper-clad laminate") having a circuit conductor (copper) formed on both sides in a wiring pattern of 1 mm square lattice (residual copper rate of 59%). After laminating the resin composition layer on the copper-clad laminate, the resin composition layer is thermally cured by vacuum pressing under the above-mentioned thermal curing conditions to obtain an insulating layer. After etching the support, the embeddability of the resin composition layer in the wiring pattern of 1 mm square lattice is observed using a FIB-SEM composite device, and the lattice pattern is embedded with the resin composition layer. The embeddability can be measured according to the method described in the examples described later.
[0200] The resin composition layer of the resin sheet is laminated on a circuit board by vacuum pressing, and the resin composition layer is thermally cured at 100°C for 30 minutes and then at 200°C for 120 minutes, resulting in a cured resin composition layer that exhibits excellent insulation reliability. Thus, the cured product provides an insulating layer with excellent insulation reliability. Specifically, the resin composition layer of the resin sheet is laminated on a glass cloth-based epoxy resin double-sided copper-clad laminate (hereinafter referred to as "copper-clad laminate") having circuit conductors (copper) formed on both sides in a 1 mm square lattice wiring pattern (residual copper rate of 59%). After laminating the resin composition layer on the copper-clad laminate, the resin composition layer is thermally cured by vacuum pressing under the above-mentioned thermal curing conditions to obtain an insulating layer. After peeling off the support, electrolytic plating is performed to obtain a conductor layer on the insulating layer. The conductor layer side is the positive electrode and the copper-clad laminate side is the negative electrode. A highly accelerated life test device is used, and the insulation resistance value after 100 hours under the conditions of 110°C, 85% relative humidity, and 20 V DC voltage application is measured six times with an electrochemical migration tester. At this time, the insulation resistance value of at least one test piece is preferably 1.00×10 8 Ω or more, preferably 1.00×10 9The average insulation resistance of the six test pieces is preferably 1.00×10 8 Ω or more, preferably 1.00×10 9 The insulation reliability can be evaluated by measuring according to the method described in the examples below.
[0201] By forming an insulating layer by vacuum press processing using the resin sheet of the present invention, an insulating layer exhibiting good embedding properties and insulation resistance value can be obtained. Therefore, the resin sheet of the present invention can be suitably used as a resin sheet for forming an insulating layer by vacuum press processing (for forming an insulating layer by vacuum press processing). The resin sheet of the present invention has a support containing a metal foil, and the metal foil can be used to form a conductor layer. Therefore, the resin sheet of the present invention can be suitably used as a resin sheet for forming both an insulating layer and a conductor layer by vacuum press processing in the manufacture of a printed wiring board (for forming an insulating layer and a conductor layer by vacuum press processing). The resin sheet of the present invention can be suitably used to form an insulating layer (and a conductor layer) of a printed wiring board, preferably an interlayer insulating layer (and a conductor layer) of a printed wiring board. In the present invention, the term "printed wiring board" also includes a rewiring board of a semiconductor package.
[0202] [Printed wiring boards and methods of manufacturing printed wiring boards] The printed wiring board of the present invention includes an insulating layer made of a cured product of the resin composition layer of the resin sheet of the present invention.
[0203] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A process of laminating a resin sheet on an inner layer substrate by vacuum pressing. (II) A step of thermally curing the resin composition layer to form an insulating layer
[0204] The "inner layer substrate" used in step (I) is a member that becomes the substrate of a printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a printed wiring board is also included in the "inner layer substrate" of the present invention. When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.
[0205] The inner layer substrate and the resin sheet are laminated by vacuum pressing so that the resin composition layer of the resin sheet is bonded to the inner layer substrate. By laminating the inner layer substrate and the resin composition layer by vacuum pressing, it is possible to improve the dielectric properties, mechanical strength, and electrical properties.
[0206] First, the inner layer substrate and the resin sheet are set in a vacuum press device so that the resin composition layer of the resin sheet and the inner layer substrate are bonded. Next, a vacuum press treatment is performed to heat and press the inner layer substrate and the resin composition layer under reduced pressure conditions. The vacuum press treatment is preferably a vacuum heat press treatment (vacuum hot press treatment) in which heat is applied.
[0207] The inner layer substrate and the resin sheet are preferably set in a vacuum press device via cushion paper, a metal plate such as a stainless steel plate (SUS plate), a release film, or the like.
[0208] The vacuum press treatment can be carried out using a conventionally known vacuum press device that presses the inner layer substrate and the resin sheet from both sides with a heated metal plate such as a SUS plate. An example of a commercially available vacuum press device is "VH1-1603" manufactured by Kitagawa Seiki Co., Ltd.
[0209] The vacuum pressing treatment may be carried out only once, or may be carried out repeatedly two or more times. When the vacuum pressing treatment is carried out repeatedly two or more times, the pressure, heating temperature, pressing time, etc. may be the same or different.
[0210] In the vacuum press treatment, the compression pressure (pressing force) is preferably 0.49 MPa or more, more preferably 0.98 MPa or more, and is preferably 7.9 MPa or less, more preferably 5.9 MPa or less.
[0211] In the vacuum press process, the atmospheric pressure, i.e., the pressure (degree of vacuum) during decompression in the chamber in which the laminated structure to be processed is stored, is preferably 3×10 -2 MPa or less, more preferably 1×10 -2 MPa or less. There is no particular lower limit, but it is 1×10 -10 MPa or more.
[0212] In the vacuum press treatment, the heating temperature varies depending on the composition of the resin composition layer, but is usually 150°C or higher, preferably 160°C or higher, more preferably 170°C or higher, or 180°C or higher. The upper limit of the heating temperature is not particularly limited, but it can usually be 240°C or lower. In addition, the vacuum press treatment may be performed while increasing the temperature stepwise or continuously and / or decreasing the temperature stepwise or continuously from the viewpoint of obtaining the effects of the present invention significantly. In addition, as described later, the resin composition layer may be thermally cured by heating in the vacuum press treatment to form an insulating layer.
[0213] In the vacuum press treatment, the pressing time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more. The upper limit is not particularly limited, but is preferably 300 minutes or less, more preferably 200 minutes or less, and even more preferably 150 minutes or less.
[0214] After laminating a resin sheet on an inner layer substrate by vacuum pressing, in step (II), the resin composition layer is thermally cured to form an insulating layer. For example, when performing pressing by vacuum hot pressing, a method of thermally curing the resin composition layer by using heat generated during pressing to form an insulating layer can be mentioned as a method of thermally curing the resin composition layer.
[0215] The conditions for thermally curing the resin composition layer are not particularly limited, and conditions that are usually employed when forming an insulating layer for a printed wiring board may be used.
[0216] For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, etc., but the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.
[0217] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. or more and less than 120° C. (preferably 60° C. or more and 115° C. or less, more preferably 70° C. or more and 110° C. or less) for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes).
[0218] The present inventors have confirmed that the uniformity of the thickness of the insulating layer may be worsened in the vacuum press treatment due to the resin flow during lamination of the resin sheet, as compared with the vacuum lamination method. In this regard, the uniformity of the thickness of the insulating layer after the vacuum press treatment can be improved by adjusting the amount of residual solvent in addition to the specific surface area of the inorganic filler in the resin composition layer and setting the maximum value of tan δ to 1.0 or more and 2.0 or less. Specifically, the variation in the thickness of the insulating layer after the heat press treatment is preferably less than ±20%, more preferably less than ±15%, and even more preferably ±10% or less, relative to the standard thickness of the insulating layer. That is, it is preferable that the insulating layer has a standard thickness in which the variation in thickness falls within the above range. The standard thickness can usually be the design thickness of the insulating layer. The lower limit can be 0%, ±0.1% or more, etc. The evaluation of the thickness of the insulating layer after the vacuum press treatment can be measured according to the method described in the examples described later.
[0219] The resin sheet used in the present invention has a support that includes a metal foil, and therefore may include, as step (III), a step of forming a circuit by a subtractive process or a modified semi-additive process.
[0220] In the step (III), a circuit can be formed by a subtractive method or a modified semi-additive method using a support (metal foil).
[0221] In the subtractive method, unnecessary parts (non-circuit forming parts) of the metal foil are selectively removed by etching or the like to form a circuit. The circuit formation by the subtractive method may be carried out according to a known procedure. For example, the circuit formation by the subtractive method can be carried out by a method including: i) providing an etching resist on the surface of the metal foil (i.e., the surface opposite to the surface bonded to the resin composition layer); ii) exposing and developing the etching resist to form a wiring pattern; iii) etching and removing the exposed metal foil parts; and iv) removing the etching resist.
[0222] In the modified semi-additive method, the non-circuit forming portion of the metal foil is protected by a plating resist, and a metal such as copper is thickly applied to the circuit forming portion by electrolytic plating, and then the plating resist is removed, and the metal foil other than the circuit forming portion is removed by etching to form a circuit. The circuit formation by the modified semi-additive method may be carried out according to a known procedure. For example, the circuit formation by the modified semi-additive method can be carried out by a method including: i) providing a plating resist on the surface of the metal foil (i.e., the surface opposite to the surface bonded to the resin composition layer), ii) exposing and developing the plating resist to form a wiring pattern, iii) electroplating through the plating resist, iv) removing the plating resist, and v) etching and removing the metal foil other than the circuit forming portion. In addition, when the metal foil is thick, the entire surface of the metal foil may be thinned by etching or the like before the above i) so that the metal foil has a desired thickness (usually 5 μm or less, 4 μm or less, or 3 μm or less).
[0223] In manufacturing a printed wiring board, a step (IV) of drilling holes and a step (V) of roughening the insulating layer may be further carried out. These steps (IV) to (V) may be carried out according to various methods known to those skilled in the art and used in manufacturing printed wiring boards. Furthermore, if necessary, the formation of the insulating layer and the conductor layer in steps (I) to (V) may be repeated to form a multilayer wiring board.
[0224] [Semiconductor Devices] The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be manufactured by using the printed wiring board of the present invention.
[0225] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft).
[0226] The semiconductor device of the present invention can be manufactured by mounting a component (semiconductor chip) on a conductive portion of a printed wiring board. The "conductive portion" refers to a portion of a printed wiring board that transmits an electric signal, and the portion may be either on the surface or embedded. The semiconductor chip is not particularly limited as long as it is an electric circuit element made of semiconductor material.
[0227] The method of mounting a semiconductor chip when manufacturing a semiconductor device is not particularly limited as long as the semiconductor chip functions effectively, but specific examples include a wire bonding mounting method, a flip chip mounting method, a bumpless buildup layer (BBUL) mounting method, an anisotropic conductive film (ACF) mounting method, a non-conductive film (NCF) mounting method, etc. Here, the "bumpless buildup layer (BBUL) mounting method" refers to "a mounting method in which a semiconductor chip is directly embedded in a recess in a printed wiring board and the semiconductor chip is connected to the wiring on the printed wiring board." EXAMPLES
[0228] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" mean "parts by mass" and "% by mass", respectively.
[0229] <Inorganic fillers used> Inorganic filler 1: Spherical silica (Denki Kagaku Kogyo Co., Ltd. "UFP-30", average particle size 0.30 μm, specific surface area 30.7 m 2 The surface was treated with 2 parts of N-phenyl-3-aminopropyltrimethoxysilane (KBM573, manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts of silica gel (100 parts per million / g). Inorganic filler 2: Spherical silica (Admatechs "SO-C1", average particle size 0.25 μm, specific surface area 11.2 m 2 The surface was treated with 1 part of N-phenyl-3-aminopropyltrimethoxysilane (KBM573, manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts of silica gel (g). Inorganic filler 3: Spherical silica (Admatechs "SO-C2", average particle size 0.50 μm, specific surface area 5.8 m 2 The surface was treated with 1 part of N-phenyl-3-aminopropyltrimethoxysilane (KBM573, manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts of silica gel (g).
[0230] <Synthesis Example 1: Synthesis of Polyimide Resin 1> A monomer composition was obtained by mixing 49.6 g of BPADA, 50.4 g of BPPAN, and 40 g of toluene as a solvent in 400 g of N,N-dimethylacetamide (hereinafter also referred to as "DMAc") as a solvent, and stirring and reacting the monomer composition at room temperature and atmospheric pressure for 3 hours. As a result, a polyamic acid solution was obtained.
[0231] Subsequently, the polyamic acid solution was heated, and the temperature was kept at about 160°C while the condensed water was azeotropically removed with toluene under a nitrogen stream. It was confirmed that a predetermined amount of water had accumulated in the water content receiver and that no water was flowing out. After confirmation, the reaction solution was further heated and stirred at 200°C for 1 hour. It was then cooled. As a result, a varnish containing 20% by mass of polyimide resin 1 as a non-volatile component was obtained.
[0232] From the above reaction pathway, it was presumed that the polyimide resin 1 contains a structural unit represented by the following formula (e1a): In addition, from the above reaction pathway, it was presumed that the polyimide resin 1 contains a first skeleton derived from BPADA and a second skeleton derived from BPPAN.
[0233] [ka]
[0234] <Synthesis Example 2: Synthesis of Elastomer 1> In a reaction vessel, 50 g of G-3000 (bifunctional hydroxyl group-terminated polybutadiene, number average molecular weight = 5047 (GPC method), hydroxyl group equivalent = 1798 g / eq., solid content 100 mass%: manufactured by Nippon Soda Co., Ltd.), 23.5 g of Ipsol 150 (aromatic hydrocarbon-based mixed solvent: manufactured by Idemitsu Petrochemical Co., Ltd.), and 0.005 g of dibutyltin laurate were mixed and dissolved uniformly. When the mixture became uniform, the temperature was raised to 50°C, and 4.8 g of toluene-2,4-diisocyanate (isocyanate group equivalent = 87.08 g / eq.) was added while further stirring, and the reaction was carried out for about 3 hours. Next, the reaction mixture was cooled to room temperature, and 8.96 g of benzophenonetetracarboxylic dianhydride (acid anhydride equivalent = 161.1 g / eq.), 0.07 g of triethylenediamine, and 40.4 g of ethyl diglycol acetate (manufactured by Daicel Corporation) were added thereto, and the mixture was heated to 130°C with stirring and reacted for about 4 hours. -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the reaction mixture was cooled to room temperature and filtered through a 100 mesh filter cloth to obtain Elastomer 1 having an imide skeleton, a urethane skeleton, and a butadiene skeleton. Viscosity: 7.5Pa s (25℃, E-type viscometer) Acid value: 16.9mgKOH / g Solid content: 50% by mass Number average molecular weight: 13723 Glass transition temperature: -10℃ Polybutadiene structural portion content: 50 / (50+4.8+8.96)×100=78.4% by mass
[0235] <Example 1: Preparation of resin composition 1> Five parts of a bixylenol type epoxy resin ("YX4000HK" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: approximately 185), five parts of a naphthalene type epoxy resin ("ESN475V" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., epoxy equivalent: approximately 332), two parts of a cyclohexane type epoxy resin ("ZX1658GS" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: approximately 135), ten parts of a phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of cyclohexanone:methyl ethyl ketone (MEK) with a solid content of 30 mass%, Mw=35,000), and ten parts of cyclohexanone were dissolved by heating with stirring. After cooling to room temperature, 4.5 parts of active ester curing agent (DIC Corporation's "HPC-8000L-65TM", active group equivalent of approximately 220, 1:1 solution of toluene:MEK with non-volatile components of 65% by mass), 35 parts of inorganic filler 1, and 0.1 part of amine curing accelerator (4-dimethylaminopyridine (DMAP)) were mixed and uniformly dispersed using a high-speed rotating mixer, and then filtered with a cartridge filter (ROKITECHNO Corporation's "SHP020") to prepare resin composition 1.
[0236] <Example 2: Preparation of resin composition 2> In Example 1, 4.5 parts of active ester curing agent (DIC Corporation's "EXB-8000L-65TM", active group equivalent of about 220, toluene:MEK 1:1 solution with 65% by mass of non-volatile components) was changed to 4.7 parts of active ester curing agent (DIC Corporation's "HP-B-8151-62T", active group equivalent of 238, toluene solution with 62% solids). Resin composition 2 was prepared in the same manner as in Example 1 except for the above.
[0237] <Example 3: Preparation of resin composition 3> In Example 3, 35 parts of Inorganic Filler 1 was changed to 50 parts of Inorganic Filler 2. Resin composition 3 was prepared in the same manner as in Example 1 except for the above-mentioned changes.
[0238] <Example 4: Preparation of resin composition 4> In Example 1, 4.5 parts of an active ester curing agent (DIC Corporation's "EXB-8000L-65TM", active group equivalent of about 220, toluene:MEK 1:1 solution with 65% by mass of non-volatile components) was replaced with 10 parts of a maleimide compound (Designer Molecules' "BMI-689"), The amount of amine curing accelerator (4-dimethylaminopyridine (DMAP)) was changed from 0.1 parts to 0.05 parts. Furthermore, 0.1 parts of a polymerization initiator ("Perhexyne 25B" manufactured by NOF Corporation) was used. Resin composition 4 was prepared in the same manner as in Example 1 except for the above.
[0239] <Example 5: Preparation of resin composition 5> In Example 4, 10 parts of the maleimide compound (Designer Molecules' "BMI-689") was replaced with 10 parts of a styrene-modified polyphenylene ether resin (Mitsubishi Gas Chemical's "OPE-2St 1200", Mn=1200, toluene solution with a solid content of 65% by mass). Resin composition 5 was prepared in the same manner as in Example 4, except for the above.
[0240] <Example 6: Preparation of resin composition 6> In Example 4, 4.5 parts of an active ester curing agent (DIC Corporation's "EXB-8000L-65TM", active group equivalent of about 220, 1:1 solution of toluene:MEK with non-volatile content of 65% by mass) was further used. Resin composition 6 was prepared in the same manner as in Example 4 except for the above.
[0241] <Example 7: Preparation of resin composition 7> In Example 6, 10 parts of a phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of cyclohexanone:methyl ethyl ketone (MEK) with a solid content of 30 mass%, Mw=35000) and 15 parts of the polyimide resin 1 obtained in Synthesis Example 1 (non-volatile component 20 mass%) were used. Resin composition 7 was prepared in the same manner as in Example 6 except for the above.
[0242] <Example 8: Preparation of resin composition 8> In Example 6, 10 parts of a phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of cyclohexanone:methyl ethyl ketone (MEK) with a solid content of 30% by mass, Mw=35000) and 6 parts of the elastomer obtained in Synthesis Example 2 (non-volatile components: 50% by mass) were used. Resin composition 8 was prepared in the same manner as in Example 6 except for the above.
[0243] <Example 9: Preparation of resin composition 9> Ten parts of a maleimide compound ("BMI-689" manufactured by Designer Molecules), 10 parts of a biphenyl skeleton-containing maleimide resin ("MIR-3000" manufactured by Nippon Kayaku Co., Ltd., a 1:1 solution of toluene:MEK with a non-volatile content of 70% by mass), 10 parts of a styrene-modified polyphenylene ether resin ("OPE-2St 1200" manufactured by Mitsubishi Gas Chemical Co., Ltd., Mn=1200, a toluene solution with a solid content of 65% by mass), and 6 parts of a hydrogenated styrene-based thermoplastic elastomer ("H1043" manufactured by Asahi Kasei Corporation, styrene / ethylene-butylene-butadiene ratio=67 / 33) were dissolved in a mixed solvent of 20 parts of solvent naphtha and 10 parts of cyclohexanone by heating with stirring. After cooling to room temperature, 50 parts of inorganic filler 1 and 0.1 parts of a polymerization initiator ("Perhexyne 25B" manufactured by NOF Corporation) were mixed thereto, and the mixture was uniformly dispersed using a high-speed rotating mixer. The mixture was then filtered through a cartridge filter ("SHP020" manufactured by ROKITECHNO Corporation) to prepare resin composition 9.
[0244] <Example 10: Preparation of resin composition 10> In Example 9, 50 parts of Inorganic Filler 1 was changed to 65 parts of Inorganic Filler 2. Resin composition 10 was prepared in the same manner as in Example 9 except for the above-mentioned changes.
[0245] <Example 11: Preparation of resin composition 11> In the preparation of Example 9, 10 parts of a styrene-modified polyphenylene ether resin ("OPE-2St 1200" manufactured by Mitsubishi Gas Chemical Co., Ltd., Mn=1200, toluene solution with a solid content of 65% by mass) was changed to 10 parts of a vinyl group-containing resin ("ODV-XET-X04" manufactured by Nippon Steel Chemical & Material Co., Ltd., weight average molecular weight 3110, 65% by mass solution). Resin composition 11 was prepared in the same manner as in Example 9 except for the above.
[0246] <Example 12: Preparation of resin composition 12> In Example 1, 4.5 parts of the active ester curing agent (DIC Corporation's "EXB-8000L-65TM", active group equivalent of about 220, toluene:MEK 1:1 solution with 65 mass% nonvolatile content) was changed to 5 parts of a triazine skeleton-containing phenolic resin (DIC Corporation's "LA7054", MEK solution with 60% solid content and hydroxyl group equivalent of about 125). A resin composition 12 was prepared in the same manner as in Example 1 except for the above.
[0247] <Comparative Example 1: Preparation of Resin Composition 13> In Example 1, 35 parts of Inorganic Filler 1 was changed to 35 parts of Inorganic Filler 3. Resin composition 13 was prepared in the same manner as in Example 1 except for the above-mentioned points.
[0248] <Comparative Example 2: Preparation of Resin Composition 14> In Example 1, the amount of the inorganic filler 1 was changed from 35 parts to 50 parts. Resin composition 14 was prepared in the same manner as in Example 1 except for the above-mentioned points.
[0249] <Comparative Example 3: Preparation of Resin Composition 15> In Example 9, 50 parts of Inorganic Filler 1 was changed to 50 parts of Inorganic Filler 3. Resin composition 15 was prepared in the same manner as in Example 9 except for the above-mentioned changes.
[0250] <Measurement of thickness of resin composition layer, etc.> The thickness of the resin composition layer etc. was measured using a contact type film thickness meter (manufactured by Mitutoyo Corporation, MCD-25MJ).
[0251] <Preparation of resin sheet A> As a support, an ultra-thin copper foil (MW-G manufactured by Mitsui Mining & Smelting Co., Ltd. (single-layer copper foil with a thickness of 12 μm, arithmetic mean roughness (Ra) of 900 nm, ten-point average roughness (Rz) of 8000 nm)) was prepared. Resin compositions 1 to 15 were uniformly applied to the ultra-thin copper foil of the support by a die coater so that the thickness of the resin composition layer after drying was 15 μm, and dried at 70 ° C to 120 ° C for 7 minutes to obtain a resin composition layer on the support. Next, a rough surface of a polypropylene film ("Alphan MA-411" manufactured by Oji F-Tex Co., Ltd., thickness 15 μm) was laminated as a protective film on the surface of the resin composition layer not bonded to the support so as to be bonded to the resin composition layer. As a result, a resin sheet A consisting of the ultra-thin copper foil (support), the resin composition layer, and the protective film in this order was obtained. The arithmetic mean roughness (Ra) and ten-point average roughness (Rz) of the ultra-thin copper foil were measured using a non-contact surface roughness meter.
[0252] <Measurement of tan δ in dynamic viscoelasticity> The dynamic viscoelasticity of the resin composition layer of the resin sheet A was measured using a dynamic viscoelasticity measuring device (UBM's "Rheosol-G3000"). 1 g of the sample resin composition taken from the resin composition layer was heated from the starting temperature of 60°C to 200°C at a heating rate of 5°C / min using a parallel plate with a diameter of 18 mm, and the dynamic viscoelasticity was measured under the measurement conditions of a measurement temperature interval of 2.5°C, a vibration frequency of 1 Hz, and a strain of 1 deg. The obtained values of E' and E'' were used to calculate tan δ using the following formula. The maximum value of tan δ at 100°C or higher was then calculated. tan δ=E'' / E'
[0253] <Evaluation of insulation layer thickness (resin flow), insulation reliability, and embeddability after vacuum press processing> 1) Lamination of the laminated sheet onto the copper clad laminate using a vacuum press As the copper-clad laminate, a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 12 μm, substrate thickness 0.15 mm, Mitsubishi Gas Chemical Company's "HL832NSF LCA", 255 × 340 mm size) was prepared, which has a circuit conductor (copper) formed on both sides in a wiring pattern of 1 mm square lattice (copper remaining rate 59%). Both sides of the inner layer circuit board were subjected to a copper surface roughening treatment (copper etching amount 0.5 μm) using MEC's "CZ8201". The protective film was peeled off from the resin sheet A to expose the resin composition layer. Next, using a vacuum hot press machine (Kitagawa Seiki Co., Ltd., VH1-1603), the exposed resin composition layer was laminated on both sides of the copper-clad laminate so that it was in contact with the copper-clad laminate. The pressing conditions were a vacuum pressure of 1 × 10 -3 The pressure is reduced to 20kgf / cm2 or less. 2 Under the above conditions, the heating conditions for the first pressing were a temperature of 100° C. and a time of 30 minutes, and for the second pressing were a temperature of 190° C. and a time of 120 minutes. After the resin composition layer was cured by heating through pressing, the support was peeled off to obtain a cured substrate A.
[0254] 2) Electroplating An electrolytic copper plating process was performed using a chemical solution manufactured by Atotech Japan under conditions that allowed copper to fill the via holes. After that, a conductor layer having lands and conductor patterns with a thickness of 10 μm was formed on the surface of the insulating layer using a land pattern with a diameter of 1 mm that was connected to the lower conductor and a circular conductor pattern with a diameter of 10 mm that was not connected to the lower conductor as a resist pattern for patterning by etching. Next, an annealing treatment was performed at 200°C for 90 minutes. This substrate was designated "Insulation Evaluation Substrate A."
[0255] 3) Evaluation of the insulation reliability of the insulating layer The 10 mm diameter circular conductor side of the insulation evaluation board A was used as the positive electrode, and the lattice circuit conductor (copper) side of the inner layer circuit board connected to the 1 mm diameter land was used as the negative electrode. Using a highly accelerated life tester (ETAC's "PM422"), the insulation resistance value after 100 hours under the conditions of 110°C, 85% relative humidity, and 20V DC voltage application was measured with an electrochemical migration tester (J-RAS's "ECM-100"). This measurement was performed six times, and the following evaluation criteria and insulation resistance values are shown in the table below. The insulation resistance values shown in the table below are the average insulation resistance values of the six test pieces. 〇: The average insulation resistance value of the six test pieces is 1.00×10 9 More than Ω. △: The average insulation resistance value of the six test pieces is 1.00×10 8 Ω or more 1.00×10 9 Less than ohms. ×: The average insulation resistance value of the six test pieces is 1.00×10 8 Less than ohms.
[0256] 4) Evaluation of insulation layer thickness (resin flow) after vacuum press processing After etching the ultra-thin copper foil of the cured substrate A, the cross section was observed using a FIB-SEM composite device ("SMI3050SE" manufactured by SII Nanotechnology Corporation), and the thickness of the insulating layer after the vacuum press treatment was evaluated according to the following criteria. ○: When the standard thickness of the insulation layer is 10 μm, the thickness of the insulation layer is less than 10 μm ± 20%. ×: When the standard thickness of the insulating layer is 10 μm, the thickness of the insulating layer is 10 μm ±20% or more.
[0257] 5) Evaluation of the embedding property of the insulating layer after vacuum pressing After etching the ultra-thin copper foil of the cured substrate A, the embeddability of the resin composition layer in the wiring pattern of 1 mm square lattice was observed using a FIB-SEM composite device ("SMI3050SE" manufactured by SII Nano Technology Corporation) and evaluated according to the following criteria. ○: The wiring pattern is buried in an insulating layer. ×: Voids are generated due to improper filling.
[0258] [Table 1] *The content of component (A) is expressed when the total amount of non-volatile components in the resin composition is taken as 100 mass %.
Claims
1. A thermosetting resin sheet for forming an insulating layer using a vacuum press process, A support and a resin composition layer provided on the support, the support has a metal foil having an arithmetic mean roughness (Ra) of more than 300 nm on the surface that is bonded to the resin composition layer; The resin composition layer has a specific surface area of 10 m 2 / g or more of inorganic filler, (B) an epoxy resin and / or (D) a radical polymerizable compound, A thermosetting resin sheet, in which a resin composition layer is heated from 60°C to 200°C at a heating rate of 5°C / min, and dynamic viscoelasticity is measured under measurement conditions of a frequency of 1 Hz and a strain of 1 deg, and the maximum value of tan δ at 100°C or higher is 1.0 or more and 2.0 or less.
2. The thermosetting resin sheet according to claim 1 , wherein the resin composition layer has a thickness of 30 μm or less.
3. The thermosetting resin sheet according to claim 1 or 2, wherein the resin composition layer contains any one of an active ester resin, a maleimide resin, and a vinyl resin.
4. The thermosetting resin sheet according to any one of claims 1 to 3, wherein the content of the component (A) is 73% by mass or less when the content of the non-volatile components in the resin composition layer is 100% by mass.
5. A thermosetting resin sheet described in any one of claims 1 to 4, wherein the content of component (A) is 50 mass% or more when the non-volatile components in the resin composition layer are 100 mass%.
6. The thermosetting resin sheet according to any one of claims 1 to 5, wherein the metal foil comprises a copper foil.
7. The thermosetting resin sheet according to any one of claims 1 to 6, wherein the support has a thickness of 9 µm or more.
8. A printed wiring board comprising an insulating layer made of a cured product of the resin composition layer of the thermosetting resin sheet according to any one of claims 1 to 7.
9. A semiconductor device comprising the printed wiring board according to claim 8.
10. (I) a step of laminating the thermosetting resin sheet according to any one of claims 1 to 7 on an inner layer substrate by vacuum pressing; and (II) a step of thermally curing the resin composition layer to form an insulating layer; A method for manufacturing a printed wiring board, comprising:
Citation Information
Patent Citations
Method for measuring dynamic viscoelasticity of particulate material
JP2013024801A
Metal-clad laminate, printed wiring board, and semiconductor device
JP2015089622A
Resin composition for insulator layer of printed wiring board
JP2015211086A
Resin composition for printed wiring board, prepreg, resin substrate, metal clad laminated board, printed wiring board, and semiconductor device
JP2016196548A
Prepreg
JP2017057352A